Toward accurate disease diagnosis of fruit trees: Integrating a novel dual-angle vegetation index with canopy vertical distribution knowledge - Wenjie Zhang; Guijun Yang; Xinlian Liang; Xiaohong Liu; Jianbo Qi; Hao Yang; Haikuan Feng; Bo Li; Changyuan Zhai; Baoguo Wu; Xiaohui Su; Liping Chen; et al. (Remote Sensing of Environment, 2026)

Investigation of endogenous and exogenous oxygen contributions and gas generation mechanisms during isothermal oxidation based on ReaxFF oxygen tracing - Hao Lu; Bo Tan; Saiyi Gao; Zhenrong Li; Peiyu Hu; Qi Tang; Shanqi Wang; Jinliang Li (Fuel, 2026)

Efficient purification of bio-oil-derived levoglucosenone via a multi-stage synergistic separation strategy - Kai Li; Yong-sheng Ma; Bo Wang; Ding-wang Qiao; Qi Niu; Cheng-long Ruan; Bi-heng Bao; Xin-hua Yuan; Qiang Lu (Biomass and Bioenergy, 2026)

Dandelion-like Pd/Cu nanozyme with multi-enzyme activities: A colorimetric sensor array for PFAS discrimination - Hui-ting Hu; Xiao-mei Li; Wen-cai Jiang; Chen Ni; Yu-yang He; Guo-qi Zhang; Hao Yu; Zhi-Bo Hou (Analytica Chimica Acta, 2026)

Extrusion-induced supramolecular disassembly of rice adjunct starch: governing enzymatic convertibility and fermentable sugar release in mashing - Lijun Jiang; Jialin Song; Mingming Qi; Jian Liu; Chengyi Sun; Bo Wang; Fengling Yue; Miaomiao Sui; Dongliang Zhang; Guihong Zhao; Hongjun Li (Food Chemistry, 2026)

Decoding the thermocyclic solar-driven fermentation: Multi-omics insights into microbial and metabolic dynamics of traditional Chishui river basin soy sauce - Wei-Qin Deng; Zhen-Ming Lu; Xiong-Bo Li; Zhi-Yi Fan; Ting Li; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Chemistry, 2026)

Multi-tissue transcriptomics reveals age-dependent susceptibility to grass carp reovirus linked to metabolic alterations and extracellular matrix disruption in grass carp - Qi Fang; Bo Wang; Yingyin Cheng; Yongming Li; Bin Gui; Wanting Zhang; Xin Guan; Yutong Fang; Mijuan Shi; Xiao-Qin Xia (Fish & Shellfish Immunology, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

A tetrahedral framework DNA-metformin nano-firefighter for quenching adipose chronic inflammation: Reprogramming macrophages to restore metabolic homeostasis in obesity - Zhuo Chen; Jiaqi Li; Alimire Alifu; Fenglin Jiang; Wenjing Tang; Zaowei Yang; Yuhao Liu; Bo Tian; Xi Chen; Yu Chen; Qi Han; Yunfeng Lin (Chemical Engineering Journal, 2026)

Synergistic d/p-band regulation of Ni-Co3Se4 electrocatalyst for high-performance lithium–sulfur batteries - Wenxuan Liu; Ziheng Wang; Jinzheng Liu; Bo Jiang; Hao Gu; Xiaodong Shao; Qi Shao; Lutong Shan; Yanhong Li; Wei Ji; Wenwu Li; Ho Seok Park (Chemical Engineering Journal, 2026)

A source-reduction process via mechanical activation assisted K2SO4 roasting and closed-loop recycling of potassium salt for efficient lithium extraction from lepidolite - Dong-qi Song; Shu-hao Dong; Long-long Zhou; Zi-ang Si; Shuai-bo Geng; Huan Li; Hui Guo (Chemical Engineering Journal, 2026)

Thermo-hydro-mechanical coupling modelling and interface effects of transplanted turf slope soil in an alpine meadow - Bo Jin; Qi Li; Xiangjun Pei; Mingzhou Li; Xiaochao Zhang; Xiaoyi Zhao (Cold Regions Science and Technology, 2026)

Corrigendum to “Linking microbial functional partitioning with methane productivity and stability in microbial electrolysis cell–anaerobic digestion hybrid systems” [Bioresour. Technol. 453 (2026) 134629] - Xue-Ting Wang; Yanxue Li; Yuxin Pan; Xue Xing; Bo Wang; Defeng Xing; Jun Nan; Jonathan Tian En Lee; Eakalak Khan; Daniel C.W. Tsang; Nan-Qi Ren; Yong Sik Ok (Bioresource Technology, 2026)

Field-scale assessment of ridging operation quality using UAV LiDAR point clouds - Chuntao Yu; Jinyang Li; Chen Zhao; Jinkai Qiu; Liqiang Qi; Bo Zhang; Wei Zhang (Computers and Electronics in Agriculture, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Research on fracture propagation characteristics and design optimization of well factory fracturing in laminated shale reservoirs - Bo Zhang; Yanlong Li; Tiankui Guo; Nengyou Wu; Minhui Qi; Jiwei Wang; Zhanqing Qu (Geomechanics for Energy and the Environment, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Carboxymethyl cellulose content optimization in an electro-responsive hydrogel for efficient swelling and superior forward osmosis draw agent performance - Xing Ji; Bo Zhang; Yuan Liang; Yu Zhang; Feng Wang; Zonghe Huang; Haoyu Zhang; Yonggang Wang; Qi Li (Desalination, 2026)

Pristimerin disrupts blood-testis barrier (BTB) integrity via ferroptosis and apoptosis by the NUR77/ATF3/CHOP pathway - Jiaqi Li; Haoyu Chen; Zhengxin Lu; Yuanbiao Ma; Shanshan Li; Zhiyu Chen; Zhewen Deng; Qi Zhang; Bo Ma (Chemico-Biological Interactions, 2026)

Correction: Spermidine Alleviates Liver Damage Induced by Iron Overload by Inhibiting Oxidative Stress - Shuo Li; Yilian Wang; Shiyu Chen; Yuxuan Qi; Yuxin Qi; Xinyi Wang; Bo Kang (Biological Trace Element Research, 2026)

Granulosa cell dysfunction is associated with MCU-mediated mitochondrial calcium dyshomeostasis and reduced AKT phosphorylation in porcine cystic follicles - Yan-Zhu Chen; Ya-Nan Sun; Bo-Qi Zhang; Jin-Xin Zong; Yu-Xin Luo; Si-Hui Wang; Ya-Qiu Li; Hong Hao; Xu Zhou; Lu Chen; Chun-Jin Li (Theriogenology, 2026)

Axial compressive behavior of double-skin stainless steel tube columns filled with High-Strength Engineered Cementitious Composites (HS-ECC) - Wei-Chen Wang; Yu-Xuan Zheng; Jia-Qi Zhou; Jun-Hua Li; Ke-Xin Weng; Yi-Nong Shen; Bo-Tao Huang (Ocean Engineering, 2026)

A BODIPY-based nanotheranostic suppresses osteosarcoma via dual photodynamic/photothermal action by disruption of YAP1/β-catenin Axis - Zhewen Deng; Mengyuan Zhang; Senqiang Zhu; Yunlong Zhang; Haitao Liao; Jiaqi Li; Peiyu Yan; Qi Zhang; Rui Liu; Bo Ma (Journal of Photochemistry and Photobiology B: Biology, 2026)

Integrating mineral-scale evidence with PMF-SHAP to interpret geogenic reservoirs and mining-enhanced trace-element dispersion in agricultural soils - Chuanfang ZHOU; Zhongfang YANG; QI Hongyun; Yanfeng SUN; Xiaoyong WEI; Zhiqiang YIN; Ruiqin CAO; Guangyuan NIU; Xuanpu ZHANG; Liming JIA; LI Bo (Journal of Hazardous Materials, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Chronic heat exposure induces brain atrophy in mice: Molecular signatures and AI-driven intervention strategy - Wenxin Xiang; Bo Yin; Qi Huang; Shisu Li; Miaohui Ding; Guoqing Feng; Ruoran Li; Dizhi Wang; Leizi Min; Xingyuan Hu; Limei Ke; Linfeng Liu; et al. (Journal of Environmental Sciences, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

Lycii Fructus-derived extracellular vesicles-like particles attenuate sodium iodate-induced retinal injury by transporting bioactive cargo molecules - Pan Huang; Xiao-Bo Zhang; Jia-Qi Li; Guan-Wen He; Ying Chen; Ling-Yun Yang; Zai-Long Chi (Chemical Engineering Journal, 2026)

Linking microbial functional partitioning with methane productivity and stability in microbial electrolysis cell–anaerobic digestion hybrid systems - Xue-Ting Wang; Yanxue Li; Yuxin Pan; Xue Xing; Bo Wang; Defeng Xing; Jun Nan; Jonathan Tian En Lee; Eakalak Khan; Daniel C.W. Tsang; Nan-Qi Ren; Yong Sik Ok (Bioresource Technology, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Decoding immunotherapy resistance in multiple myeloma: genetic insights and approaches to counter resistance - Huan Li; Qi Xia; Mei Yu; Ying Lv; Jialing Xiao; Xiaoxin Guo; Kai Dong; Yu Zhou; Ling Zhong; Ting Wang; Weijia Wu; Chengzi Gan; et al. (Science China Life Sciences, 2026)

Identification of GNSS spoofing interference causing position deviation based on hierarchical clustering - Han Gao; Fuping Sun; Weidong Sun; Qi Li; Lundong Zhang; Peiyuan Zhou; Bo Jiao (Advances in Space Research, 2026)

Effects of GIAHS conservation on agricultural landscape and ecological sustainability in heritage sites: evidence from the Yuanyang Hani Rice Terraces - Jin-Rong Zhang; Hong-Bo Li; He-Ping Yang; Meng-Na Qi (Environment, Development and Sustainability, 2026)

Spermidine Alleviates Liver Damage Induced by Iron Overload by Inhibiting Oxidative Stress - Shuo Li; Yilian Wang; Shiyu Chen; Yuxuan Qi; Yuxin Qi; Xinyi Wang; Bo Kang (Biological Trace Element Research, 2026)

Pre-adaptive resistance to acequinocyl associated with cross-resistance to bifenazate in field populations of Tetranychus urticae across China - Jin-Cui Chen; Hui-Juan Li; Ming Xue; Bo Peng; Jing-Jing Kang; Qi-Yu Chen; Shuai-Yu Wang; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2026)

Molecular characterization of Echinococcus granulosus EGR-02244 and its functional role in canine peripheral blood mononuclear cells - Juncheng Huang; Yanyan Zhang; Xinwen Bo; Xinwei Feng; Jing Li; Xuke Cheng; Jiaxin Zhao; Jianan Zhao; Bing Li; Linying Wei; Yan Sun; Meng Qi; et al. (Veterinary Parasitology, 2026)

Microbial lifestyles driven by C: N stoichiometric imbalance govern responses of carbon metabolism to nitrogen addition - Bo Kang; Rong Huang; Xun Yan; Linkang Chen; Shanghong Chen; Youlin Luo; Xiaoyan Tang; Yingjie Wu; Qi Tao; Qiang Xu; Changquan Wang; Bing Li (Soil Biology and Biochemistry, 2026)

Mapping the iceberg: from focal trauma to a spectrum of systemic complications in spinal cord injury - Chi Zhang; Enlin Qi; Chuang Li; Yufei Du; Mingxin Wu; Ruizhi Jiang; Shaolong Li; Dongqi Tang; Zhenfeng Li; Bo Chu; Hengxing Zhou; Shiqing Feng (Science Bulletin, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Carbohydrate conversion and microbial community restructuring following Saccharomyces cerevisiae inoculation during Pu-erh tea fermentation - Ruoyu Li; Teng Wang; Qiuyue Chen; Yanhui Guan; Nianguo Bo; Qi Wang; Yiqing Guan; Dihan Yang; Ping Liang; Yan Ma; Tiejun Ling; Ming Zhao (International Journal of Food Microbiology, 2026)

Decoding the dynamic formation of bolus: A multimodal fusion and simulation framework for texture perception-regulated oral processing - Che Shen; Xinyu Jiang; Lizhang Wu; Zidong Chen; Zihao Li; Ran Wang; Wenxi Qi; Yi Zhang; Xinying Zhou; Bo Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

Gastric pH-induced liquid–liquid phase separation between lactoferrin and osteopontin protects against proteolysis and modulates intestinal uptake - Lan Liu; Chenming Lin; Meidan Zheng; Xinyue Tu; Yaming Yu; Zehan Song; Guoqiang Qi; Shanshan Li; Mingying Yang; Bo Lönnerdal; Yajun Shuai (Food Research International, 2026)

Genome-wide Identification of Shaker-type K+ Channels in Alfalfa and the Role of MsSKOR in NaHCO3-induced Alkaline Stress Tolerance - Yao Tongtong; Li Huijiao; Xu Jiaxuan; Wang Kexin; Zhang Zhe; Zhang Hongjiao; Zhang Hongrui; Qi Siyue; Su Bing; Liu Xinying; Qin Bo; Zhang Huihui (Journal of Plant Growth Regulation, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

High-resolution mapping reveals spatiotemporal dynamics and scaling law of industrial carbon emissions in China - Ziyan Liu; Wei Liu; Qi Feng; Meng Zhu; Yuanyuan Xue; Lingge Wang; Xinwei Yin; Bo Wang; Yingqing Su; Xianglong Gao; Xin Yan; Jutao Zhang; et al. (Resources, Conservation and Recycling, 2026)

Elevated CO2 accelerates mineral-protected organic carbon loss in the upland rhizosphere after paddy drainage - Xun Yan; Zhifan Li; Bo Kang; Tao Li; Linkang Chen; Junwen Zhao; Bing Li; Youlin Luo; Yingjie Wu; Rong Huang; Xiaoyan Tang; Qiang Xu; et al. (CATENA, 2026)

Andrographolide induces testicular damage by triggering ferroptosis in Sertoli cells via disruption of β-TrCP-mediated ATF4 ubiquitination and degradation - Jiaqi Li; Zhengxin Lu; Nan Zhang; Xiaowei Zhou; Yuanbiao Ma; Jia-qi Li; Yimu Zhang; Zhewen Deng; Na Lin; Peng Yue; Yilin Yang; Qi Zhang; et al. (Chemico-Biological Interactions, 2026)

Integrated multi-omics and experimental validation for identifying novel biomarkers of acute myocardial infarction - Siyuan Qu; Qi Nie; Jiaxi Li; Bo Zhang; Ziqiang Chen; Liya Zhou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Brucellosis vaccine development: immunological mechanisms, animal models, and future directions - Yi Zhang; Dongwei Li; Bo Wang; Xiao Li; Yansong Qi; Haitao Ding (Archives of Microbiology, 2026)

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

The major chemical constituents of Penthorum chinense Pursh and their inhibitory activity against enzymes associated with metabolic dysfunction-associated steatotic liver disease - Chao-Qun Wang; Meng-Qi Wang; Xiao-Na Gan; Ting-Zhao Li; Xiang-Wei Zheng; Bo Li; Xin Fang; Shuang Liang (Natural Product Research, 2026)

Co-existence of blaCTX-M and mcr-1 in avian pathogenic Escherichia coli in Southern Xinjiang: current status and antimicrobial resistance characteristics - Bin Yang; Guofeng Xing; Wenxuan Ma; Meng Qi; Bo Jing; Jing Li; Jing Wu (Folia Microbiologica, 2026)

Shift in orbital-scale climate response under the coupling of ice sheet and monsoon during the Late Oligocene: Sedimentary records from the East China Sea Shelf Basin - Yingkun Cui; Fujie Jiang; Xianke He; Yichen Liu; Wenji Wang; Rui Zhang; Yinghui Liu; Zhuo Li; Zhenguo Qi; Bo Xu; Hang lv; Jiming Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

First record of mammal fossil from the lower Oligocene Tala Formation, Linxia Basin, Gansu, China - Yong-Tao Quan; Shi-Qi Wang; Hai-Yan Qi; Tong Zhang; Li-Bo Pang; Shao-Kun Chen (Palaeoworld, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Low-carbon renovation of old residential blocks: An envelope-focused assessment framework for carbon reduction effects and economic benefits - Shen Xu; Yichen Dong; Hongxin Guo; Zhen Yu; Bo Pan; Congyue Qi; Gaomei Li (Energy and Buildings, 2026)

Critical role of nickel in selectivity control of reactive adsorption desulfurization of thiophene on Cu/ZnO sorbent - Fanjing Wei; Bo Liu; Hao Qin; Ting Li; Guisheng Qi; Weizhou Jiao; Hongyan Shen; Zhiguo Yuan; Youzhi Liu (Chemical Engineering Journal, 2026)

Flexible and multimodal sensing platforms for wearable respiratory monitoring: Innovations in materials and systems for precision health - Xiang-Jun Zha; Qi-Kun Li; Peng Chen; Ying Liu; Jigang Huang; Jian-Bo Li; Yang Zhou (Chemical Engineering Journal, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Influence of Water on the Generation of Hydrogen-Containing Products in Coal Spontaneous Combustion Based on Radioactive Hydrogen Isotope Tracing - Tianze Li; Bo Tan; Liyang Gao; Jiliang Huang; Qi Tang; Tianyao Chang; Xiaomeng Li; Feiran Wang (Natural Resources Research, 2026)

Land cover change and its influencing factors in the Southeast Xizang Autonomous Region, China - Binghua Zhang; Linshan Liu; Yili Zhang; Bo Wei; Huxiao Qi; Dianqing Gong; Changjun Gu; Lanhui Li (Journal of Mountain Science, 2026)

Agroforestry balances plant–soil–microbe–enzyme interactions and improves its connectivity and homeostasis: Evidence from C:N:P stoichiometric networks - Qi-Wen Xu; Meng-Die Feng; Tian-Yang Li; Lin Xiong; Bo-Yu Ren; Yan-Zheng He; Bing-Hui He (Agriculture, Ecosystems & Environment, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Impact of coupled climate change and human exploitation on groundwater dynamics in agricultural intensive planting areas - Jiajun Li; Bo Li; Peng Qi; Zhijun Li; Yunfei Bai (Groundwater for Sustainable Development, 2026)

Self-supporting characteristics in hierarchical monolith catalyst with highly accessible active sites for boosting lean methane catalytic oxidation - Xin Xu; Wenge Liu; Hongtai Liu; Yunliang Li; Xiaoyang Gao; Bo Lu; Jian Qi; Zhi Li; Jiaye Han; Yuan Yan (Fuel, 2026)

Occurrence, drivers, and risk assessment of non-antibiotic pharmaceuticals in urban sewer systems - Fan Meng; Shaojing Sun; Jialu Cheng; Ziyi Wang; Changshun Wang; Jinpan Jiang; Lu Lu; Jingchao Li; Yajie Tian; Lixin Ma; Bo Li; Xiaoyu Feng; et al. (Environmental Pollution, 2026)

Flexible and compressible thermoelectric foam for temperature–pressure dual sensor - Po-Shen Lin; Meng Li; Yong-Qi Chen; Bo-Xuan Hu; Cheng-Liang Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2026)

Reductive Dechlorination of Trichloroethene by Carboxymethyl Cellulose Stabilized and Sulfidated Nanoscale Zero-Valent Iron: Effect of Humic Acid - Bo Chen; Qi Li; Yuhan Hang; Si Chen; Zihan Xie; Hao Yuan; Yadong Yang; Feng He (Water, Air, & Soil Pollution, 2026)

Combined with wavelet time frequency analysis and lightweight deep convolutional networkintelligent recognition of coal rock acoustic emission signal - Zhong-kai Peng; Wei-jian Liu; Zhi-zeng Zhang; Zhen-xia Yuan; Shi-lei Zhen; Zhuang-zhuang Wang; Xin-bo Luan; Jian-bo Li; Hao-yang Li; Bi-qi Yuan; Shuai Teng; Zi-wei Li (Applied Geophysics, 2026)

Experimental Investigation of Macro- and Microscopic Degradation and Damage Mechanisms in Granite Subjected to Microwave Radiation under True Triaxial Compression - Sheng-Qi Yang; Bo-Wen Sun; Heng Li (Rock Mechanics and Rock Engineering, 2026)

Breaking redox compromise in real scale up wastewater with Cr(VI) and antibiotic: Interfacial charge regulation mechanism - Hao Du; Bo Shen; Jie Zhang; Qin Jin; Qiang Li; Zhe Zhang; Derek Hao; Liguo Shen; Qi Wang (Water Research, 2026)

Polymorphisms of XKR4 and ANGPTL4 genes and their association with growth traits in Hu sheep - Qijia Dai; Xiaobin Yang; Qi Zhang; Chengqi Yan; Lianjun Feng; Yukun Zhang; Deyin Zhang; Zongwu Ma; Yanchao Li; Hongmei Hou; Tong Cai; Bo Ma; et al. (Small Ruminant Research, 2026)

Phylogenomic framework, biogeography and character evolution of the genus Campylotropis (Fabaceae, Papilionoideae) - Li-Sha Jiang; Yu Feng; Jun-Yi Zhang; Xiong Li; Min Liao; Heng-Ning Deng; Qi Yu; Bo Xu (Molecular Phylogenetics and Evolution, 2026)

Mechanistic insight into curcumin-induced conjugative plasmid transfer acceleration: Role of intracellular arginine uptake - Min-ge Wang; Kai-di Liu; Wen-jie Jin; Run-bo Li; Jun-qi Liu; Liang-xing Fang; Jian Sun; Xiao-ping Liao (Food Microbiology, 2026)

Accurate prediction and screening of Ni-based bimetallic catalysts for hydrogen production from biogas reforming: An interpretable machine learning study - Wen-ming Zhang; Bin Hu; Bo-yuan Zheng; Ji Liu; Qi Niu; Kai Li; Zhi-mo Fang; Bing Zhang; Qiang Lu (Chemical Engineering Journal, 2026)

Sulfone site enables H2O2 practical fabrication over metal-free photocatalyst - Zhi-Peng Tao; Lin Liu; Ke-Chao Wang; Chen-Ning Li; Jia-Qi Chu; Zhen-Hui Kang; Zheng-Bo Han (Chemical Engineering Journal, 2026)

Machine learning-assisted sensor array based on enhanced dual enzyme-like activities of Fe SAzymes modulated via Pluronic surfactant for multi-category perfluoroalkyl intelligent recognition and quantification - Wen-Cai Jiang; Xiao-Mei Li; Jia-Hao Cheng; Li-Yao Xu; Ri-Za He; Gui-Lin Zou; Zhi-Bo Hou; Yan Zhao; Guo-Qi Zhang (Chemical Engineering Journal, 2026)

Oridonin exposure induces testicular impairment through regulating ferroptosis via HIF-1α/HO-1 activation and STUB1-driven GPX4 ubiquitination-dependent degradation - Zhongchi Xu; Jiaqi Li; Yuyang Hou; Zhewen Deng; Qi Zhang; Bo Ma (Chemico-Biological Interactions, 2026)

Secondary metabolites from the arial parts of Hyssopus cuspidatus Boriss. and their chemotaxonomic significance - Jian-Kang Lu; Gui-Juan Zheng; Jing-Jing Li; Xiao-Xia Jiang; Jin-Xin Zhan; Chang-Hao Yu; Xu Wang; Yi-Xuan Zeng; Tian-Jiao Qi; Hong Liu; Hui-Ming Peng; Jin-Bo Fang (Biochemical Systematics and Ecology, 2026)

Causal links between pandemics and weather and air pollution in 39 cities, 2020–2021 - Ting Shi; Bo Zhou; Ailin Qi; Kai Wang; Yunpeng Ao; Chenyi Li; Yuling Zhang (Atmospheric Pollution Research, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

A persistent luminescent lateral flow immunoassay for rapid and accurate detection of estradiol in real samples - Chao Huang; Bingni Jia; Runqi Jiang; Qi Li; Xiaofeng Liu; Caicheng Long; Peng Zhang; Bo Feng; Taiping Qing (Analytica Chimica Acta, 2026)

Effects of Shifts in Bacterial Community on Improving Water Quality and Growth Performance of Pacific Whiteleg Shrimp (Litopenaeus vannamei) in Biofloc Systems - Hai-Hong Huang; Chao Cheng; Li-Li Guo; Wan-Sheng Zou; Yan-Ju Lei; Wei-Qi Kuang; Bo-Lan Zhou; Pin-Hong Yang; Chao-Yun Li (Fishes, 2025)
This study aimed to induce a shift in a bacterial community by adding substrate into a biofloc system to characterize this shift and estimate its benefits in improving water quality and aquatic animal growth. We compared the bacterial communities between two biofloc systems, either with (sB treatment) or without (nB treatment) the addition of substrate (elastic solid packing filler), and we also analyzed the effects of the shift on the water quality and growth performance of shrimp (Litopenaeus vannamei). Beta diversity analysis indicated that the bacterial communities in the two treatments were significantly different (Jaccard index 0.94 ± 0.01, pseudo-F = 3.96, p = 0.001). The addition of substrate showed significant positive effects on bacterial alpha diversity indices (Shannon, Heip, Pielou, and Simpson; p

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Carbon dioxide and water exchanges of a Qinghai spruce forest ecosystem in the Qilian Mountains in Northwestern China - Guanlong Gao; Qi Feng; Erwen Xu; Yulian Hao; Rongxin Wang; Wenmao Jing; Xiaofeng Ren; Junxi Shi; Bo Wu; Yujing Wen; Yin Wang; Qingyun Li (Journal of Hydrology, 2025)

Triphenylamine-based fluorescent probes for lipid droplet detection and non-alcoholic fatty liver disease identification - Jing-Yi Li; Ya-Tong Liu; Zhi-Bo Jiang; Si-Yi Yao; Fan-Qi Shen; Yu-Yang Wang; Yue-Li Zou; Li-Xia Zhao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Evaluating the impact of “source-sink" landscape composition and configuration changes on sediment yield in watersheds using a coupled multi-model framework - Hao Yang; Zixuan Qi; Wei Huang; Bo Li; Guanhui Cheng; Yanpeng Cai (Journal of Cleaner Production, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Nitrogen-doped cobalt-copper carbide as a PMS activator for efficient pollutant degradation via a 1O2-dominated non-radical mechanism - Ruoyao Zhang; Bo Shen; Zhuomin Xiang; Leyi Li; Suxiang Guo; Hao Du; Qi Wang; Jun Li (Environmental Research, 2025)

Multifunctional SIS-PEG-AC bio-patch with enhanced adhesion, sustained anti-inflammatory activity, and regenerative properties to promote lung repair - Heng Li; Deguang Wang; Zixun Wang; Wenjie Chen; Yuxin Guo; Han Liang; Yanqiu Zhao; Qi Wang; Yiqian Huang; Wei Jing; Pengfei Wei; Bo Zhao; et al. (Chemical Engineering Journal, 2025)

Cellular indexing of transcriptomes and epitopes by sequencing unveils coordinated RNA and protein landscape in ovary at single-cell resolution - Yujuan Qi; Yuxuan Feng; Xiaoyan Liu; Jiaxin Li; Qiuru Huang; Zhenbei Li; Sen Zheng; Ning Chen; Jie Cheng; Xinhui Yang; Wei Tao; Xiangnan Cao; et al. (Chemical Engineering Journal, 2025)

Fracture Characteristics and Quantitative Analysis of Anisotropic Rock with Direction-Arranged Minerals Subjected to Triaxial Cyclic Loading: A Case of Biotite Quartz Schist - Han Bao; Yankai Wang; Changqing Liu; Qun Qi; Hengxing Lan; Shengwen Qi; Bo Li; Peng Sha; Hongtao Lv (Rock Mechanics and Rock Engineering, 2025)

The osteoclast blind spot and other unresolved mechanisms in the exosomal theory of tuberculosis-induced osteoporosis - LiSheng Qi; QinWen Gu; Bo Chen; DuJiang Yang; DongDong Li (Immunologic Research, 2025)

Solar drying of cyanobacterial waste enhanced by phase change materials: Process optimization and kinetic modeling - Die Wang; Chujie Qi; Yuchen Yang; Li Gao; Qirui Zhou; Bo Bian (Algal Research, 2025)

Cost-benefit analysis of remanufacturing of used agricultural machinery parts in China - Jia-qi Shen; Zong-yi Zhang; Hong-bo Li (Journal of Cleaner Production, 2025)

A multiscale peridynamic simulation on thermal-mechanical coupling behavior and damage failure mechanism of granite - Heng Li; Sheng-Qi Yang; Rui Yong; Shi-Gui Du; Bo-Wen Sun; Su-Sheng Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Comprehensive analysis of microbial communities, metabolites, and biogenic amines in bagged fermented chili paste at varying salt levels - Wei-Qin Deng; Zhen-Ming Lu; Ze-Liang Wang; Si-Qiang Jiang; Xiong-Bo Li; Zhi-Yi Fan; Xiao-Juan Zhang; Li-Juan Chai; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Bioscience, 2025)

Self-gel formation and improvement mechanisms of silver carp surimi by Lactiplantibacillus plantarum based on microbial metabolism - Chunsheng Li; Jiangping Chen; Xiaoxia He; Yongqiang Zhao; Bo Qi; Xue Zhao; Hui Huang (Food Bioscience, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Nitrogen-doped hydrothermal carbon as a catalyst for selective alkoxyphenol production from pine pyrolysis - Dong-hong Nan; Cheng-bo Zhang; Qi Niu; Shi-yu Feng; Bin Hu; Ji Liu; Kai Li; Qiang Lu (Biomass and Bioenergy, 2025)

Expression of LGALS3 and XPNPEP2 genes and their association with growth traits in sheep - Guoxing Jia; Weimin Wang; Huibing Tian; Xiaojuan Wang; Yukun Zhang; Yuan Zhao; Lijuan He; Zongwu Ma; Xioabing Yang; Dan Xu; Kunchao Han; Peiliang Cao; et al. (Tropical Animal Health and Production, 2025)

Experimental Study on the Mechanical Behavior and Fracturing Mechanism of Red Sandstone Under Triaxial Monotonic and Multilevel Cyclic Loading - Sheng-Qi Yang; Ke-Sheng Li; Bo-Wen Sun; Wen-Ling Tian (Rock Mechanics and Rock Engineering, 2025)

Hydrodynamic coefficient of tuna longline hook, bait and baited hook based on flume tank test - Bo Zhang; Liming Song; Yuwei Li; Yukun Qi; Linhui Wang; Meng Zhang; Hailin Hao (Fisheries Science, 2025)

Mn-doped carbon dots-based fluorescent-colorimetric dual-mode probes for selective and sensitive detection of Cr(VI) ions and l-ascorbic acid via smartphone-integrated analytical platform - Shan Huang; Wenqian Zhang; Bo Li; Guixin Li; Wei Ni; Yi Fang; Fuxiang Wei; Qi Xiao (Analytica Chimica Acta, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Study on numerical simulation analysis methods of multi-layer discontinuous rammed earth structure - Qiangqiang Pei; Bo Zhang; Pan Qi; Jianzhong Zhao; Wenjun Li; Wenwu Chen (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

A comprehensive review of advancements in vanadium electrolyte preparation for Vanadium Redox Flow Batteries - Muneeb Ul Hassan Naseer; Bo Pan; Shaona Wang; Yeqing Lyu; Biao Liu; Lanjie Li; Jian Qi; Hao Du (Journal of Environmental Chemical Engineering, 2025)

Solid-liquid phase equilibria of ternary system NH4+, Ca2+ // SO42-- H2O at 323.2 and 348.2K, and its application in the comprehensive utilization of waste secondary gypsum - Changhao Wu; Xudong Yu; Nan Zhang; Jing Li; Qi Li; Yousheng Yang; Ke Chen; Bo Yang; Shuang Wang; Yiping Liu; Zhenwen Xing (Journal of Environmental Chemical Engineering, 2025)

The evolution and research hotspots of perfluorinated compounds (PFCs): Health risks, environmental behavior, and collaborative effort - Jing-Xuan Zhou; Xiong-Bo Liu; Zi-Yi Zheng; Li-Chun Qiao; Yi Hu; Kaiyao Hu; Xuming Liu; Xiang Jia; Wenhao Qi (Journal of Environmental Chemical Engineering, 2025)

Ion intercalation engineering in crystalline C3N5 for efficient photosynthesis of H2O2 - Bolun Li; Ling Zhou; Xiaoying Bo; Huimin Wei; Jiaoyan Li; Shuijing Wang; Chunxue Liu; Qi Xu; Caijie Yang; Hengming Huang; Jiahui Kou; Chunhua Lu (Journal of Environmental Chemical Engineering, 2025)

Synthesis of furfurylamine and its derivative N-(furan-2-ylmethyl) acetamide from renewable biomass via chemobiocatalytic cascade catalysis - Qi Li; Junhua Di; Bo Fan; Yu-Cai He; Yu Deng (Chemical Engineering Journal, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Study on the antioxidant defense of Pacific oysters (Crassostrea gigas) against sulfonamide antibiotics - Hao Chen; Liping You; Jing Sun; Hao Yu; Wei Sun; Changlin Song; Bo Su; Chenglong Ji; Lin Ye; Shujun Li; Yanmin Qi; Yuanqing Ma (Aquaculture, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Crustal growth from collision to post-collision: implications from Cretaceous back-arc magmatism flare-up in southern Qiangtang of central Tibet - Sheng-Qiang Zhang; Neng Gong; Hui Qi; Yun-Chuan Zeng; Guo-Li Yuan; Pei-Pei Dong; Ying-Jie Li; Gen-Hou Wang; Zhi-Bo Liu; Xiao Liang (Lithos, 2025)

Interfacial electric field steering S-scheme charge transfer in MIL-88A(Fe)/polydopamine Heterojunctions: Dual-redox pathways for efficient pollutant mineralization - Bo Shen; Hao Du; Aoxiang Liu; Ningyi Li; Cheng Chen; Liguo Shen; Yuxin Hui; Rubin Huo; Zhe Zhang; Qi Wang (Journal of Cleaner Production, 2025)

Nature-Inspired cell membrane-coated artificial biocatalysts with Os-single-atom sites and multienzyme-Mimetic activities for targeted tumor therapy - Jiawei Wang; Jing Wu; Zijun Ma; Xin Xie; Lu Zhao; Xiao Luo; Wenjun Liu; Bo Ren; Qi Li; Ling Li; Shengdong Mu (Chemical Engineering Journal, 2025)

Engineered exosomal miR140 modulates mitophagy of chondrocytes through targeting CAPN1 to alleviate osteoarthritis - Yuan Liu; Kai Huang; Sheng-Liang Zhou; Shuai Li; Hai-Bo Si; Yi Zeng; Hui-Qi Xie; Bin Shen (Science China Life Sciences, 2025)

The phenylalanine synthesized by whitefly–Portiera symbiosis enhances host survival under fungi infection - Chao Lv; Song-Xue Zhang; Ji-Sheng Hong; Tian-Yu Wang; Bing-Qi Liu; Chu-Qiao Li; Jin-Yang Yan; Jun-Bo Luan (Journal of Pest Science, 2025)

A NIR Isophorone-based Zinc Coordination Fluorescence Probe for the Detection of Glyphosate and Application in Environment, Food and Living Systems - Si-Yi Yao; Han-Wen Cui; Zhi-Bo Jiang; Hao Wang; Jing-Yi Li; Yu-Yang Wang; Fan-Qi Shen; Li-Xia Zhao; Ya-Tong Liu; Yue-Li Zou (Journal of Fluorescence, 2025)

Two new chemical constituents from the aerial parts of Tripterygium wilfordii - Xia Zhang; Lei Huang; Yu-Jun Tang; Ya-Lin Hu; Wei Xu; Hong-Yu Li; Yu-Bo Zhang; Xiao-Qi Zhang; Guang-Xiong Zhou (Natural Product Research, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

3,4-seco-Prenyllabdane sesterterpenoids and 3,4-seco-labdane diterpenoids with Zika virus inhibitory potential from Callicarpa nudiflora - Xue-Wen Wu; Guan-Rong Qiao; Xue-Rong Zhao; Qi Li; Muhammad Aurang Zeb; Xiao-Li Li; Chang-Bo Zheng; Wei-Lie Xiao (Phytochemistry, 2025)

Addressing non-Gaussian noise in AUV navigation: The role of MSTTKF and IMM techniques - Xiaona Sun; Bo He; Ziyun Chen; Qi Wang; Pinchi Li (Ocean Engineering, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Biological denitrification driven by hydrochar: Insight into the mechanism from intracellular and extracellular electron transfer - Shengjie Chen; Zequan Cao; Zhu Wang; Qing Yong; Wei Peng; Fubing Yao; Kun Luo; Bo Li; Dongbo Wang; Xiaoming Li; Qi Yang (Journal of Environmental Chemical Engineering, 2025)

Cultured biomass enhances the flavor and nutrition characteristics of biomass/plant hybrid cultured meatballs - Zi-Qing Meng; Chang-Bo Tang; Tian-yi Tao; Wenjuan Song; Chun-Bao Li; Jun Qi; Shi-jie Ding; Guang-Hong Zhou (Food Research International, 2025)

Enhanced Nutrient Release and Microbial Activity: Assessment of Ca-P mineral enriched biochar loaded with Paenibacillus mucilaginosus - Yanjiao Qi; Jiazhi Gao; Shen Yang; Qian Li; Linshan Wang; Bo Zhang; Yidan Duan; Huining Lu; Lan Wu; Hong Zhang; Yamin Zhao (Water, Air, & Soil Pollution, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Optimal land sharing/sparing pattern to synergize grain yield and ecosystem services of cropland: A case study of Chengdu, China - Shuruo Li; Xiaobin Jin; Bo Han; Yaxuan Feng; Shuxin Wu; Zhao Qi; Xiaolin Zhang; Yinkang Zhou (Applied Geography, 2025)

Upcycling algal biomass into biodegradable materials: Enhancing structural properties and performance through hydrophobic modifications - Yuchen Yang; Chujie Qi; Runhao Zhang; Yongze Li; Ganpei Tian; Li Gao; Bo Bian (Algal Research, 2025)

Ultra-processed foods, biological ageing, and all-cause mortality risk: a prospective cohort study using 172,225 participants from UK Biobank - Yifan Wang; Tianchen Qi; Xiaoli Wu; Chunhao Li; Boyan Zeng; Peiqi Huang; Dan Liu; Shuang Liang; Fan Yang; Feifei Xu; Chang Su; Bo Zhang; et al. (GeroScience, 2025)

Deep reinforcement learning algorithm incorporating problem characteristics for dynamic multi-objective permutation flow-shop scheduling problem - Yuan-Yuan Yang; Bin Qian; Rong Hu; Zuocheng Li; Zi-Qi Zhang; Huai-Ping Jin; Jian-Bo Yang (Swarm and Evolutionary Computation, 2025)

Microbial taxonomic diversity and functional genes mirror soil ecosystem multifunctionality in nonferrous metal mining areas - Meng-yao Zheng; Xiao-jun Qi; Zhi-yue Liu; Yi-ting Wang; Yan-bo Ren; Yuan Li; Yue Zhang; Bao-feng Chai; Tong Jia (Journal of Hazardous Materials, 2025)

Rapid cross-linking of MoS2 photothermal layers and their assembly of interface evaporators for desalination and environmental optimization - Zekun Zhang; Xiuling Li; Guangqi Liu; Shuo Qi; Jing Lv; Bo Ge; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Desalination, 2025)

An innovative red-emitting nickel-doped carbon dot for simultaneous detection of Fe(III) and pyrophosphate ions, coupled with synergistic photothermal/photodynamic cancer therapy - Shan Huang; Wenqian Zhang; Bo Li; Guixin Li; Wei Ni; Yi Fang; Qi Xiao (Analytica Chimica Acta, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Ambient air pollution and the risk of cancer: Evidence from global cohort studies and epigenetic-related causal inference - Dong Peng; Xiao-Yu Liu; Yuan-Hui Sheng; Si-Qi Li; Dan Zhang; Bo Chen; Pei Yu; Zhao-Yuan Li; Shuai Li; Rong-Bin Xu (Journal of Hazardous Materials, 2025)

Atomically selective Bi doping in tetragonal phase of Zn0.5Cd0.5S twins with efficient utilization of photogenerated electrons and holes for dual functional photocatalytic reactions - Yuxin Liu; Yiqiang He; Yuhang Qi; Zhe Zhang; Chunguang Li; Xiao-bo Chen; Jianrong Zeng; Zhan Shi; Shouhua Feng (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Adaptive classification of landslide displacement evolution states through multi-landslide data transfer learning - Xuhuang Du; Cheng Lian; Youping Li; Zhiyong Qi; Zhengyang Tang; Jin Yuan; Bo Xu; Hui Zeng (Natural Hazards, 2025)

UAV-Based Thermal Infrared Imaging Technology: A Novel Approach for Rapid Investigation of High-Steep Slopes - Han Yin; Wen Zhang; Jia Wang; Junqi Chen; Chen Cao; Qi Sun; Tengyue Li; Bo Han (Journal of Earth Science, 2025)

Three-Dimensional Shallow P-wave Velocity Distribution in the Source Area of the 2021 MS6.0 Luxian Earthquake from Dense Array Seismic Imaging - Jian-xun Yang; Qi-yan Yang; Da-hu Li; Yong-ming Lu; Ping-ping Wu; Hui-li Guo; Ning-bo Jiang; Mi Gao; Heng Pan (Applied Geophysics, 2025)

Hydrochar-nanocomposite membrane combined hydrothermal pretreatment for nutrient upcycling from anaerobic digestate - Runhao Zhang; Chujie Qi; Jiaxin Bai; Li Gao; Stephen Gray; Chenhao Ma; Qiao Zhou; Bo Bian (Water Research, 2025)

Construction of the relationship between phytochemicals and gene expression in different Chaenomeles speciosa (Sweet) Nakai cultivars - Ya-Fang Shang; Jun-Hao Miao; Jia Zeng; Si-Qi Sun; Xiao-Long Ni; Zhao-Jun Wei; Yi-Long Ma; Hong-Xing Su; Wen-Bo Bai; Xiang-Li Niu; Wan Zhang (South African Journal of Botany, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Exceptional visible-light photocatalytic activity induced by lattice distortion in medium-entropy perovskite oxide La0.5Sr0.5Fe0.5Ti0.5O3 - Hongfang SHEN; Congcong MA; Zhihong QI; Jiaqi DING; Dong LI; Bo MA; Xiao ZHANG; Guozhong CAO; Youjun LU (Journal of Environmental Chemical Engineering, 2025)

Review of NO removal at low temperature by solid-state oxidizing denitrifier: Denitrifier, mechanism, estimation - Silan Li; Gaoshan Xing; Bo Wang; Jingxin Li; Liqiang Qi (Journal of Environmental Chemical Engineering, 2025)

Separation of oil–water emulsion by biomimetic polycaprolactone tannic acid hydrophilic modified membranes - Bingfan Li; Bo Qi; Jiang Han; Xiaowen Qian; Chao Yang; Shaomin Cai (Fuel, 2025)

Thermal-fluid coupled fracture behavior of fissured granite in a 3D crystal model - Heng Li; Sheng-Qi Yang; Bo-Wen Sun; Zhen Yang; Zhi-Jin Dong; Pin-Qiang Mo (Engineering Geology, 2025)

Short-Term Water Level Prediction for Long-Distance Water Diversion Projects Using Data-Driven Methods with Multi-Scale Attention Mechanism - Xinyong Xu; Zixuan Zhu; Xiaonan Chen; Bo Wang; Xianliang Liu; Li Jiang; Zhenbao Wang; Yuxian Qiu; Laike Yang; Xu Qi; Hao Lu (Water Resources Management, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

Tailored large-particle quantum dots with high color purity and excellent electroluminescent efficiency - Bo-Chen Liu; Qizhong Lin; Shuang-Qiao Sun; Qi Sun; Xing Peng; Xinyuan Chen; Yang Li; Yue-Min Xie; Shuit-Tong Lee; Man-Keung Fung (Science Bulletin, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

MOFs-derived porous carbon embedded Fe0 nanoparticles as peroxymonosulfate activator for efficient degradation of organic pollutants - Jia-Qi Zhou; Huan-Yan Xu; Bo Li; Bao-Ying Wang; Yue Liu; Zhi-hao Zhao; Yan-Li Zhuang (Environmental Research, 2025)

Photo-driven cycling electro-Fenton catalysis via the synergistic effect of dual cathodes for energy-efficient water decontamination: Insights into performance, reaction mechanism and toxicity - Qi Wang; Yuxin Hui; Xin Ma; Aoxiang Liu; Bo Shen; Xiaojia Jiang; Xiujuan Tang; Chunjuan Li; Yanling Wu; Jun Li; Huayue Zhu; Zhe Zhang; et al. (Chemical Engineering Journal, 2025)

Spinal PTP1B Regulated NMDA Receptor-mediated Nociceptive Transmission and Peripheral Inflammation-induced Pain Sensitization - Shu-Jin Wu; Xin-Yi Lan; Yue Shi; Yan-Ni Liu; Xiao-Xi Zhang; Qi Zhang; Yu-Bo Gao; Juan Li; Xian Yang; Hu-Hu Bai (Molecular Neurobiology, 2025)

Radiomics-based Modelling Unveils Cerebellar Involvement in Parkinson’s Disease - Yini Chen; Yiwei Qi; Yiying Hu; Tao Qiu; Meichen Liu; Qiqi Jia; Yubing Sun; Xinhui Qiu; Bo Sun; Zhanhua Liang; Weidong Le; Tianbai Li (The Cerebellum, 2025)

Human activities affecting the species richness of urban spontaneous herbs under a three-scale factor framework - Juanjuan Zhao; Zepeng Bai; Bo Jiang; Haidong Yu; Chundi Chen; Xiancui Dai; Qi Li; Chenchen Song; Nan Jiang (Urban Forestry & Urban Greening, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Bioassay-guided isolation of terpenoids from Rubus rosifolius - Yihao Yin; Jiehui Li; Qi Cao; Jinxiu Yu; Baoli Chen; Zhigang She; Xiuping Zhang; Bo Wang (Phytochemistry Letters, 2025)

Insights into P-doping effect of the activity and anti-SO2/H2O poisoning of V2O5-MoO3/TiO2 catalysts for NH3-SCR - Silan Li; Bo Wang; Zijing Liang; Liqiang Qi (Journal of Environmental Chemical Engineering, 2025)

Synergistic effect of 2′-Fucosyllactose or galactooligosaccharide with Bifidobacterium bifidum DNG6 improves the intestinal barrier by modulating the SCFAs-TLR4/NF-κB cascade response in DSS-induced colitis in mice - Cui-Cui Sun; Yu-Qi Wang; Xin-Yu Wang; Guo-Fang Zhang; Hong-Fang Cao; Ge Song; Li-Bo Liu; Chun Li; Irina Valeryevna Boyarineva; Peng Du (Food Bioscience, 2025)

Experimental analysis on breaching mechanism of earth-rock dam induced by landslide generated waves - Zhen-han Du; Jia-Wen Zhou; Shi-Chen Zhang; Qi-Ming Zhong; Hai-Bo Li; Yu-Xiang Hu; Cong-Jiang Li; Jie-Yuan Zhang (Engineering Geology, 2025)

Advanced fabrication of three-dimensional bicontinuous MXene/agarose composite monoliths for high-selective rapid separation of antibodies - Xiang-Dong Xu; Jing Li; Jun-Qi Zhang; Yuan Peng; Chen-Mei Sun; Ru-Qi Liang; Jian-Bo Qu (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Multi-objective optimization design of double-hooked corrugated plate dryer based on NSGA-II - Zhong Shuting; Sun Rulei; Li Yang; Qin Qi; Deng Chaojun; Wang Bo; Tian Ruifeng (Annals of Nuclear Energy, 2025)

The improvement and validation of laser induced fluorescence technology on temperature and concentration measurement - Qi Zhang; Haoyu Wang; Junlong Li; Yang Xu; Bo Zhao; Feipeng Qi; Bo Zhang; Dongyang Li; Sichao Tan (Annals of Nuclear Energy, 2025)

Numerical Simulation Analysis and Research on Drag Reduction and Stability Enhancement Effect of Head Swing Based on Biomimetic Flexible Variants - Debo Qi; Yang Li; Baisheng Yang; Zhengyang Wu; Bo Li; Shichao Niu (Journal of Marine Science and Engineering, 2025)
With the intensification of the oil crisis, research on drag reduction technologies has gained increasing momentum. In tidal environments, the drag reduction effectiveness of conventional methods, such as bionic non-smooth surfaces, super-hydrophobic surfaces, biomimetic jet flow, wall surface vibration, etc., will be severely diminished. To enhance the adaptability of vehicles in variable fluid environments, this study explores the feasibility of adjusting the drag of a vehicle through active head swing variants. The flexible oscillation of the head of the vehicle was achieved by combining dynamic mesh technology with User-Defined Functions (UDFs). The oscillation process was numerically simulated using Fluent software. The results show that, when the vehicle maintains a stationary posture, biasing the vehicle’s head towards the incoming flow direction can effectively reduce the radial drag and drag moment, thereby improving the stability of the vehicle. Conversely, both the radial drag and the drag moment significantly increase. This condition can be utilized for the auxiliary turning of the vehicle. When the vehicle undergoes continuous periodic oscillation of its head, the drag characteristics are optimal with the sine oscillation mode. By adjusting the range of the head’s oscillation angle, it can further minimize the average radial drag during the head swing process, making it possible to achieve radial drag reduction and enhance the vehicle’s stability through head oscillation. This research significantly improves the stability of the vehicle in tidal environments, making it adaptable to the highly variable underwater flow conditions.

Simultaneous Quantification of Total Antibody and Conjugated Payload for DS001 in Rat Serum Using a Hybrid Immuno-Capture LC–MS/MS - Xiong Yu; Weiqiang Li; Wensi Huang; Bo Xiao; Jing Long; Qi Wang; Guifeng Wang; Chunhe Wang; Mingming Yu; Jinghua Yu; Xingxing Diao (The AAPS Journal, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Regularization by double complementary priors for full waveform inversion - Hongyu Qi; Zhenwu Fu; Yang Li; Bo Han; Longsuo Li (Computers & Geosciences, 2025)

Scalable, flexible and hierarchically porous Janus membrane inducing Zn-Ion flux redistribution and desolvation for dendrite-free zinc anodes - Jiawei Mu; Miao Yu; Bo Zhao; Yan Dai; Tiantian Li; Xiangcun Li; Xinhong Qi; Xuri Wang; Gaohong He (Chemical Engineering Journal, 2025)

Ingenious microfluidic-microwave integrated biosensor for cell sorting and concentration detection of mixed white blood cells and yeasts solution - Yuan-Bo Li; Yan-Xiong Wang; Sen Yang; Qian-Long Chen; Zhong-Hao Li; Jun-Ge Liang; Qi-Gao Fan; Yan-Feng Jiang; Xiaoman Zhou; Tian Qiang (Chemical Engineering Journal, 2025)

Selective electroreduction of CO2 to CH4 by Zr-based metal–organic framework integrated binuclear copper cluster - Xuejing Zhai; Shanshan Liu; Luyang Zuo; Qi Liu; Bo Li; Liya Wang (Chemical Engineering Journal, 2025)

Sustainable dual-cathode photoelectro-Fenton system enabling oxidative and reductive removal of pollutants via visible light driving Fe sites conversion - Aoxiang Liu; Xin Ma; Bo Shen; Hao Du; Xiaojia Jiang; Yanling Wu; Yanxian Jin; Jun Li; Huayue Zhu; Qi Wang (Chemical Engineering Journal, 2025)

Constructing chromium-tolerance La0.6Sr0.4Co0.2Fe0.8O3-δ cathode for solid oxide fuel cells using entropy-assisted surface engineering - Xu Han; Qi Shao; Kaixin Li; Yuan Gao; Bo Wei; Zimin Cai; Kun Zheng; Peizhong Feng; Zhe Lv; Yihan Ling (Chemical Engineering Journal, 2025)

Time-Dependent Transcriptional Dynamics of Contextual Fear Memory Retrieval Reveals the Function of Dipeptidyl Peptidase 9 in Reconsolidation - Wen-Ting Guo; Wen-Xing Li; Yu-Chen Liu; Ya-Bo Zhao; Lin Xu; Qi-Xin Zhou (Neuroscience Bulletin, 2025)
Numerous studies on the formation and consolidation of memory have shown that memory processes are characterized by phase-dependent and dynamic regulation. Memory retrieval, as the only representation of memory content and an active form of memory processing that induces memory reconsolidation, has attracted increasing attention in recent years. Although the molecular mechanisms specific to memory retrieval-induced reconsolidation have been gradually revealed, an understanding of the time-dependent regulatory mechanisms of this process is still lacking. In this study, we applied a transcriptome analysis of memory retrieval at different time points in the recent memory stage. Differential expression analysis and Short Time-series Expression Miner (STEM) depicting temporal gene expression patterns indicated that most differential gene expression occurred at 48 h, and the STEM cluster showing the greatest transcriptional upregulation at 48 h demonstrated the most significant difference. We then screened the differentially-expressed genes associated with that met the expression patterns of those cluster-identified genes that have been reported to be involved in learning and memory processes in addition to dipeptidyl peptidase 9 (DPP9). Further quantitative polymerase chain reaction verification and pharmacological intervention suggested that DPP9 is involved in 48-h fear memory retrieval and viral vector-mediated overexpression of DPP9 countered the 48-h retrieval-induced attenuation of fear memory. Taken together, our findings suggest that temporal gene expression patterns are induced by recent memory retrieval and provide hitherto undocumented evidence of the role of DPP9 in the retrieval-induced reconsolidation of fear memory.

Multi-well plate-based versatile platform for online fabricating alginate hydrogel microspheres and in-situ 3D cell culture - Ziwei Zhang; Longyu Chen; Hongliang Wang; Bo Tang; Yongqiang Cheng; Meijia Zhu; Xiaotong Li; Xiaoxiao Qi; Yifan Shao; Xi Zhang (Analytica Chimica Acta, 2025)

Correction: Magnesium Ions Promote In Vitro Rat Bone Marrow Stromal Cell Angiogenesis Through Notch Signaling - Haotian Qin; Jian Weng; Bo Zhou; Weifei Zhang; Guoqing Li; Yingqi Chen; Tiantian Qi; Yuanchao Zhu; Fei Yu; Hui Zeng (Biological Trace Element Research, 2024)

Heavy metal stabilization via copyrolysis of comodified vermiculite with municipal sludge/aged refuse: Comprehensive analysis of hazards and characteristics of multiple coexisting heavy metals - Yuxuan Yang; Zhaoping Zhong; Houhu Zhang; Meng Qiao; Zongao Zhen; Yifan Xu; Baosheng Jin; Bo Zhang; Haoran Du; Qian Li; Xiang Zheng; Renzhi Qi; et al. (Journal of Hazardous Materials, 2024)

Hydrothermal treatment of pig manure for the catalytic production of nitrogen-phosphorus-potassium (NPK)-rich artificial humic acid and full utilisation of residue adsorption - Jiamin Qi; Shunyu Yin; Haohao Bian; Xing Fan; Junhao Huang; Bo Yang; Hengxi Zhu; Dehui Kong; Yi Zhang; Chao Yang; Yizhao Li; Zhenxing Zhou; et al. (Journal of Environmental Chemical Engineering, 2024)

Study on the carbon sequestration performance and barrier mechanism of biochar cement-based vertical cutoff walls for phenol pollution in groundwater - Wenjing Tang; Changwen Ye; Qi Zhang; Jie Li; Fang Ao; Bo Zheng; Yi Luo (Journal of Environmental Chemical Engineering, 2024)

Two-stage Mesozoic oceanic subduction and related mantle metasomatism beneath the South Qiangtang terrane with implications for post-collisional magmatism - Neng Gong; Sheng-Qiang Zhang; Hui Qi; Guo-Li Yuan; Jun Li; Gen-Hou Wang; Xiao Liang; Zhi-Bo Liu (Gondwana Research, 2024)

Effective removal of Cr(VI) from water by ball milling sulfur-modified micron zero-valent iron：Influencing factors and removal mechanism - Jianhua Qu; Huiyao Li; Ziwei Li; Wei Peng; Bo Wang; Huiru Wang; Guangshan Zhang; Qi Hu; Lei Wang; Ying Zhang (Environmental Research, 2024)

Long-term effects including shrinkage and interfacial creep on bond behavior of concrete-filled steel tubes (CFST): Experiment and design - Bo Li; Wen-Qi Xie; Fa-Cheng Wang (Engineering Structures, 2024)

Revealing critical factors in the separation of organic and inorganic anions through electrodialysis using back propagation neural networks - Huachun Pan; Mingyue Yan; Bo Wu; Yongkang Zhou; Hongyu Jin; Yingna Jia; Qi Chen; Zhikan Yao; Xuesong Zhao; Zhongjian Li; Yang Hou; Lecheng Lei; et al. (Desalination, 2024)

Sustainable dual-cathode photoelectro-Fenton-like system at a wide pH range for rapid degradation of emerging pollutants - Qi Wang; Aoxiang Liu; Bo Shen; Xin Ma; Yanling Wu; Xiaojia jiang; Jun Li; Chunjuan Li; Xiujuan Tang; Derek Hao; Huayue Zhu; Hao Du (Chemical Engineering Journal, 2024)

Two new furanone derivatives from the endophytic fungus Byssochlamys sp. and their cytotoxic activities - Jie Wang; Wen-Bin Gao; Fan-Wei Liu; Qi Liu; Bo Song; Jin Ye; Ying Chen; Cai-Lin Zhao; Wei Dong; Li-Na Guo; Bo Song (Natural Product Research, 2024)

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Functional diversification of contact calls contribute to the cohesion of a multi-level society - Yi-Jun Yang; Ying Yan; Gu Fang; Yu-Ting Song; Jing Zang; Wen-Yong Tian; Dai-Bo Zhu; Paul A. Garber; Bao-Guo Li; Xiao-Guang Qi (Behavioral Ecology and Sociobiology, 2024)

A new removal method of yellow-rotten leaf for hydroponic lettuce with the flipping-tearing-twisting trajectory and its parameters optimisation - Yidong Ma; Chong Qi; Liming Zhou; Xin Jin; Bo Zhao; Xinping Li (Biosystems Engineering, 2024)

The associations of cold spells with human mortality in Shanghai, China - Shan Jin; Xing Bi; Caiyan Wu; Bo Fang; Qi Li; Chunfang Wang; Conghe Song; Junxiang Li (Urban Climate, 2024)

Unveiling the synergism and reaction pathway of ethyl acetate removal in DBD/absorption integrated reactor - Li-qiang Qi; Lin Huang; Jia-yue Lei; Rui Dai; Fan Du; Bo Wang; Jing-xin Li; Feng Liu (Process Safety and Environmental Protection, 2024)

A new paradigm for whole-chain low-carbon utilization of food waste secondary waste based on multivariate evaluations - Yazhou Tang; Yongze Li; Runhao Zhang; Kai Zhou; Wenxiang Zhou; Chujie Qi; Bo Bian (Journal of Environmental Management, 2024)

Seasonal variation of antioxidant bioactive compounds in southern highbush blueberry leaves and non-destructive quality prediction in situ by a portable near-infrared spectrometer - Jianbo Qi; Shuai Sun; Liuqiang Zhang; Yilin Zhu; Huiji Zhou; Xiaona Gan; Bo Li; Yiling Chen; Wei Li; Tingzhao Li; Yiming Li; Gangqiang Dong; et al. (Food Chemistry, 2024)

Blood mercury mediates the associations between fish consumption and serum uric acid levels among Chinese adults: A nationally representative study - Changzi Wu; Bing Wu; Yingli Qu; Hui Fu; Yue Chen; Yifu Lu; Saisai Ji; Liang Ding; Zheng Li; Qi Sun; Miao Zhang; Xu Zhang; et al. (Environmental Research, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Formation of flake-like DAAF crystals with tunable size realized on a microfluidic platform for binder-free initiator explosives - Bo Yang; Shengshu Xi; Simin He; Jin Chen; Wei Cao; Rui Li; Rupeng Bu; Xiaona Huang; Jincan Zhu; Qi Wu; Weimiao Wang; Xiaodong Li; et al. (Chemical Engineering Journal, 2024)

Magnitude and hotspots of soil erosion types during heavy rainstorm events on the Loess Plateau: Implications for watershed management - Bo Yang; Xiaowu Ma; Juying Jiao; Wenting Zhao; Qi Ling; Jianjun Li; Xinhan Zhang (CATENA, 2024)

Response Mechanism of Dynamic Tensile Mechanics in Granite Under Microwave Irradiation: Insights from Experiments and Simulations - Bo-Wen Sun; Sheng-Qi Yang; Man Huang; Heng Li; Wen-Ling Tian; Yan-Hua Huang (Rock Mechanics and Rock Engineering, 2024)

Thyroxine regulates pig Sertoli cell line proliferation and maturation through the IKK/NFκB and p38 MAPK signaling pathways - Jing Li; Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Chun-Yan Bai; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

Antibiotics suppress the expression of antimicrobial peptides and increase sensitivity of Cydia pomonella to granulosis virus - Zaiyuan Li; Lan Ouyang; Yin Lu; Qi Peng; Xi Qiao; Qiang Wu; Bin Zhang; Bo Liu; Fanghao Wan; Wanqiang Qian (Science of The Total Environment, 2024)

Advanced soft-sensing techniques for predicting furnace temperature in industrial organic waste gasification - Mingyue Yan; Huiyang Bi; HuanXu Wang; Caicai Xu; Lihao Chen; Lei Zhang; Shuangwei Chen; Xuming Xu; Qi Chen; Yingna Jia; Bo Wu; Zhongjian Li; et al. (Process Safety and Environmental Protection, 2024)

Effect of lead exposure on silkworm midgut: Insights into oxidative gene expression, digestive function, and microbial community structure - Yan-Xia Shi; Dan-Dan Bian; Fan-Xing Chen; Ye Jin; Qi Jiang; Qiu-Ning Liu; Bo-Ping Tang; Li-Shang Dai (Process Safety and Environmental Protection, 2024)

Disinfection of bacteria and viruses under near infrared light by tunable self-assembled nanomaterial NH2-MIL-101-xAu based on photothermal and photodynamic mechanisms - Nian Li; Zi-jian He; Jia-min Gan; Xing-rui Qi; Shu-nuo Bian; Yu-fang Chen; Bo Liu; Hua-jie Lai; Tao Jin (Journal of Environmental Chemical Engineering, 2024)

Integrated A/O-MBR–NF process for treating high COD content wastewater from traditional Chinese medicine - Jinhui Xu; Jiaoyue Qiu; Xuanru Chen; Qi Li; Ruixiang Ying; Yanan Kong; Shijie Jin; Yan Yang; Yue Zhang; Chao Li; Jianguo Shao; Fagen Zhu; et al. (Journal of Environmental Chemical Engineering, 2024)

Phase inversion of bigels tuned by the concentration of soy protein isolate in the binary hydrogel matrix - Ling-Zhi Su; Ying-Xin Chen; Shi-Qi Zhang; Chun Hu; Jun-Bo He; Wei-Nong Zhang; Li-Juan Han (Food Hydrocolloids, 2024)

Rhizosphere microorganisms from the soil around the roots of Lycium barbarum L. - Zhi-bo Jiang; Ya-fei Ren; Yun-qi Hu; Jing-ling Yang; Ji-yuan Wei; Xiao-li Ma (Acta Physiologiae Plantarum, 2024)

Novel separate aeration self-circulating technology for continuous aerobic granular sludge process: Performance evaluation, hydrodynamic simulation and control strategy - Wei-Kang Qi; Run-Feng Tian; Bo Li; Shu-Jun Zhang; Yong-Zhen Peng; Cong Wang (Water Research, 2024)

Identification of LRRC46 as a novel candidate gene for high myopia - Lingxi Jiang; Chao Dai; Yao Wei; Bo Zhao; Qi Li; Zhengzheng Wu; Liang Zou; Zimeng Ye; Zhenglin Yang; Lulin Huang; Yi Shi (Science China Life Sciences, 2024)

Genomic profiling of biosynthetic potentials of medicinal secondary metabolites for ‘Aliisedimentitalea scapharcae’ KCTC 42119T, isolated from ark shell - Jin-Cheng Rong; Lin-Lin Cui; Na Li; Mao-Li Yi; Bo-Tao Huang; Qi Zhao (Marine Genomics, 2024)

Methanogenic biodegradation of thermoplastic poly(vinyl alcohol) films produced by two manufacturing processes in enrichment cultures - Ming-Le Ji; Yi-Fan Liu; Yu Bai; Zhen Hu; James H. Wang; Jia-Yi Li; Wan-Qi Qin; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Yingcheng Li; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

Triptolide induced spermatogenesis dysfunction via ferroptosis activation by promoting K63-linked GPX4 polyubiquitination in spermatocytes - Jiaqi Li; Dezhi Chen; Jialiang Suo; Jiaqi Li; Yimu Zhang; Yu Wang; Zhewen Deng; Qi Zhang; Bo Ma (Chemico-Biological Interactions, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Unveiling the facet-dependent activity of Cu2O for enhanced selective electroreduction of nitric oxide to ammonia and Zn-NO batteries - Shuang Liu; Linghui Yan; Qi Chen; Bo Wu; Heyang Zhu; Shaodong Zhou; Xiaodan Wang; Xuesong Zhao; Chen Sun; Youzhi Li; Lecheng Lei; Zhongjian Li; et al. (Process Safety and Environmental Protection, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

A robust metal–organic framework for simultaneous C2H4/C3H6 capture and C2H2/CO2 separation - Yang Chen; Dongxiao Yang; Yi Wang; Qi Shi; Bo Tang; Chongqin Zhu; Jinping Li; Libo Li (Fuel, 2024)

Combustion and emission characteristics of a gasoline/ammonia fueled SI engine and chemical kinetic analysis of NOx emissions - Shang Liu; Zhelong Lin; Yunliang Qi; Guoxiang Lu; Bo Wang; Li Li; Zhi Wang (Fuel, 2024)

Synthesis of Co3O4/BiOBr/BiOI Ternary Heterostructure and its Photocatalytic Degradation of RhB - Bo Wang; Lin Huang; Silan Li; Liqiang Qi (Water, Air, & Soil Pollution, 2024)

Effect of initial moisture content, resulting from different ratios of vegetable waste to maize straw, on compost was mediated by composting temperatures and microbial communities at low temperatures - Shanshan Sun; Cheng Guo; Jianyu Wang; Li Ren; Jianping Qu; Qi Guan; Nongxiao Dou; Jiahui Zhang; Qiuhua Chen; Qi Wang; Jiguang Wang; Jieming Li; et al. (Chemosphere, 2024)

Adsorption behavior of CuO doped GeS monolayer on the thermal runaway gas evolution in lithium battery energy storage systems - Jinjie Wang; Bo Lin; Ping Wang; Lu-Qi Tao; Yuan Zhang; Siquan Li (Journal of Environmental Chemical Engineering, 2024)

New model of nutrient utilization and salt regulation of anaerobic digestate from food waste - Yongze Li; Chujie Qi; Yazhou Tang; Bo Liu; Bo Bian; Li Gao; Linhua Fan; Zhenzhen Zhao (Desalination, 2024)

Chemical constituents from Strobilanthes cusia and their chemotaxonomic significance - Si-Qi Huang; Chao-Tian He; Qiu-Ying He; Gui-Shuai Lang; Hong-Jie Chen; Li-Ping Teng; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2024)

High-level production of chitinase by multi-strategy combination optimization in Bacillus licheniformis - Zhimin Qi; Bo Lei; Min Xiong; Weijia Li; Yongqing Liao; Dongbo Cai; Xin Ma; Ruibin Zhang; Shouwen Chen (World Journal of Microbiology and Biotechnology, 2024)

3D gravity inversion using cycle-consistent generative adversarial network - Shu-Bo Qiao; Hou-Pu Li; Rui Qi; Yu-Jie Zhang; Shi-Min Xie (Applied Geophysics, 2024)

The formation mechanism of low-angle loess-mudstone seismic landslides - Da Peng; Jingshan Bo; Wenhao Qi; Chaoyu Chang; Xiaobo Li; Yushi Duan (Soil Dynamics and Earthquake Engineering, 2024)

Zinc as a potential regulator of the BCR-ABL oncogene in chronic myelocytic leukemia cells - Bo Zhu; Longshuo Sun; Zhonghua Li; Pengyou Shang; Chunhao Yang; Kaiqiang Li; Jiahuang Li; Qi Zhi; Zichun Hua (Journal of Trace Elements in Medicine and Biology, 2024)

Preparation of monocyclic aromatic hydrocarbons from industrial lignin residue and polyethylene co-pyrolysis by microwave-assisted in fluidized bed based on bimetal-loaded HZSM-5/MCM-41 core-shell catalyst - Xiang Zheng; Zhaoping Zhong; Bo Zhang; Haoran Du; Wei Wang; Qian Li; Yuxuan Yang; Renzhi Qi; Qihang Ye; Zhaoying Li (Fuel, 2024)

Corrigendum to “Necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage” [Food Chem. Toxicol. 178 (2023) 113915] - Jiayu Du; Xuliang Zhang; Jian Zhang; Siming Huo; Bo Li; Qi Wang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2024)

Identification of particle distribution pattern in vertical profile via unmanned aerial vehicles observation - Zhi-Heng Chen; Bo-Wen Li; Bai Li; Zhong-Ren Peng; Hai-Chao Huang; Jun-Qi Wu; Hong-Di He (Environmental Pollution, 2024)

Enhanced near-infrared absorption of Cs0.32WO3 nanoparticles for efficient interfacial solar steam generation - Bo Yang; Hui Quan; Haoran Pei; Wenjing Wang; Min Zhang; Qiangchun Liu; Weiguang Han; Fangyuan Zhang; Xueqin Zuo; Guang Li; Sheng-Qi Guo (Chemical Engineering Journal, 2024)

Superabsorbent carboxymethyl cellulose–based hydrogel fabricated by liquid-metal-induced double crosslinking polymerisation - Qi Cao; Jing Chen; Miao Wang; Zhigang Wang; Wenjun Wang; Yanqin Shen; Ying Xue; Bo Li; Yanli Ma; Yijun Yao; Hailiang Wu (Carbohydrate Polymers, 2024)

Probing into the radiative mechanisms and drivers influencing urban heat-cold islands and urban pollution islands during heavy-haze events in a cold megacity of Northeast China - Stephen Dauda Yabo; Lu Lu; Lixin Ma; Bo Li; Donglei Fu; Fan Meng; Jinpan Jiang; Xie Shengjin; Wei Zhang; Hong Qi (Atmospheric Research, 2024)

Correction to: BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2024)

A new diterpenoid from the leaves and twigs of Croton lachnocarpus Benth - Xiao-Qing Zhan; Qian Wu; Mei-Jie Wang; Li Liu; Wen-Bo Cui; Feng-Li An; Feng-Ming Qi; Dong-Qing Fei; Zhan-Xin Zhang (Natural Product Research, 2024)

Effective stabilization of heavy metals in solid waste and sludge pyrolysis using intercalated-exfoliated modified vermiculite: Experiment and simulation study - Yuxuan Yang; Zhaoping Zhong; Baosheng Jin; Bo Zhang; Haoran Du; Qian Li; Xiang Zheng; Renzhi Qi; Pengkun Ren; Zhaoying Li (Waste Management, 2024)

Explainable ensemble machine learning revealing the effect of meteorology and sources on ozone formation in megacity Hangzhou, China - Lei Zhang; Lili Wang; Dan Ji; Zheng Xia; Peifan Nan; Jiaxin Zhang; Ke Li; Bing Qi; Rongguang Du; Yang Sun; Yuesi Wang; Bo Hu (Science of The Total Environment, 2024)

A novel strategy for urban and rural organic waste utilization with outstanding integrated benefits: based on study in China's Taihu Lake region - Runhao Zhang; Yongze Li; Chujie Qi; Bo Liu; Kai Zhou; Yuchen Yang; Hui Dai; Zhenzhen Zhao; Bo Bian (Journal of Cleaner Production, 2024)

Stabilization of heavy metals in solid waste and sludge pyrolysis by intercalation-exfoliation modified vermiculite - Yuxuan Yang; Zhaoping Zhong; Baosheng Jin; Bo Zhang; Haoran Du; Qian Li; Xiang Zheng; Renzhi Qi; Pengkun Ren (Journal of Environmental Management, 2024)

Structure-induced interfacial activation convoying the CO-relayed conversion of CO2 to dimethyl carbonate - Shu-Guo Han; Shenghua Zhou; Xiaofang Li; Jianqiang Zhao; Wen-Bo Wei; Lirong Zheng; Dong-Dong Ma; Xin-Tao Wu; Qi-Long Zhu (Chemical Engineering Journal, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Investigating the spatio–temporal characteristics of lower atmospheric ducts across the China seas by performing a long–term simulation using the WRF model - Qi Liu; Xiaofeng Zhao; Jing Zou; Tong Hu; Zhijin Qiu; Bo Wang; Zhiqian Li; Chaoran Cui; Rui Cao (Frontiers in Marine Science, 2024)
In this work, a diagnostic scheme for lower atmospheric ducts was established based on the Weather Research and Forecasting (WRF) model. More specifically, a 10-year simulation test was conducted for the China seas to investigate the spatio-temporal characteristics of the lower atmospheric ducts phenomenon. Compared with the sounding data, the long-term simulations showed a high temporal correlation and the root mean square error of the modified atmospheric refractivity remained between 4 M and 7 M. Based on the simulations, significant regional differences in the occurrence probability of lower atmospheric ducts were detected from south to north. Among them, the surface ducts near the sea surface exhibited the highest occurrence probability, with higher probabilities being recorded in autumn and winter, and the probability gradually increased with the decreasing latitude. The spatio-temporal characteristics of duct height, thickness, and strength were generally consistent. In the seas at mid-latitudes, strong ducts mostly occurred in the spring and autumn, with the single-layer ducts being predominant and the first layer duct showing stronger characteristics than the second layer. In the lower latitude regions, the situation was exactly the opposite. The first duct layer, which existed throughout the year, exhibited weaker characteristics with less pronounced seasonal variations. On the other hand, the second duct layer demonstrated stronger features.

New solution for predicting the removal efficiency of organic contaminants by UV/ H2O2: From a case study of 1H-benzotriazole - Juan Dang; Ling Lin; Li-ao Gao; Lin Qi; Shi-bo Zhang; Qing-zhu Zhang; Shuai Tian (Science of The Total Environment, 2024)

Establishing the global isoscape of leaf carbon in C3 plants through the integrations of remote sensing, carbon, geographic, and physiological information - Xiang Wang; Guo Chen; Joseph Awange; Yongze Song; Qi Wu; Xiaowei Li; Edmund February; Gustavo Saiz; Ralf Kiese; Xing Li; Jingfeng Xiao; Xiaoxiang Zhao; et al. (Remote Sensing of Environment, 2024)

Biodegradation of polyethylene terephthalate by Tenebrio molitor: Insights for polymer chain size, gut metabolome and host genes - Lei He; Shan-Shan Yang; Jie Ding; Cheng-Xin Chen; Fan Yang; Zhi-Li He; Ji-Wei Pang; Bo-Yu Peng; Yalei Zhang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu (Journal of Hazardous Materials, 2024)

Intelligent multi-objective optimization of 3D printing low-carbon concrete for multi-scenario requirements - Song-Yuan Geng; Qi-Ling Luo; Bo-Yuan Cheng; Li-Xiao Li; Dong-Chang Wen; Wu-Jian Long (Journal of Cleaner Production, 2024)

Experimental, numerical and analytical analysis of a single-span steel portal frame exposed to fire - Guo-Biao Lou; Jing Hou; Hong-Hui Qi; Yaqiang Jiang; Bo Zhong; Yansong Pang; Guo-Qiang Li (Engineering Structures, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Integrating the confinement effect and bimetallic cycles in a hierarchical Co3O4@Co3O4/Fe3O4 yolk-shell nanoreactor for peroxymonosulfate activation enhancement - Bo Li; Huan-Yan Xu; Gu-Hao-Nan Chi; Li-Min Dong; Lian-Wei Shan; Li-Guo Jin; Yan-Li Zhuang; Mao-Chang Cao; Xiu-Lan He; Shu-Yan Qi (Chemical Engineering Journal, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Elucidating the mechanisms underlying astrocyte-microglia crosstalk in hippocampal neuroinflammation induced by acute diquat exposure - Changcun Qi; Yuandong Yan; Qi Cao; Lingyun Zou; Shanshan Li; Qiuyu Yang; Qing Deng; Bailin Wu; Bo Song (Environmental Science and Pollution Research, 2024)

Sedimentary record of microplastics in coastal wetland, eastern China - Yujie Zhou; Shenglu Zhou; Sophia Shuang Chen; Yan Li; Long Chen; Qi Zhang; Bo Su; Teng Wang (Water Research, 2024)

Discovery of bioactive polycyclic polyprenylated acylphloroglucinols with adamantine/homoadamantane skeletons from Hypericum wilsonii - Bo Tao; Yongqi Li; Zhengyi Shi; Yulin Duan; Yi Guo; Xinye Huang; Jie Li; Yeting Zhang; Ming Chen; Fei Song; Xueqi Lan; Weiguang Sun; et al. (Phytochemistry, 2024)

A comprehensive review of wax deposition in crude oil systems: Mechanisms, influencing factors, prediction and inhibition techniques - Bingfan Li; Ziyuan Guo; Liming Zheng; Erxiu Shi; Bo Qi (Fuel, 2024)

Suggested method of utilizing soil arching for optimizing the design of strutted excavations - Ben-Guo He; Bo Lin; Hong-Pu Li; Shi-Qi Zhu (Tunnelling and Underground Space Technology, 2024)

Chlorogenic acid ameliorates the heat stress-induced impairment of porcine Sertoli cells by suppressing oxidative stress and apoptosis - Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Yu-Wei Yang; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

Whole-body aging mediates the association between exposure to volatile organic compounds and osteoarthritis among U.S. middle-to-old-aged adults - Hao-long Zhou; Dong-sheng Di; Zhang-bo Cui; Ting-ting Zhou; Ting-ting Yuan; Qian Liu; Jian-li Zhang; Xiao Luo; Dan-yang Ling; Qi Wang (Science of The Total Environment, 2024)

Quantitative simulationSimulation of nitrogen doping effects on benzene selective adsorption by activated carbon in aqueous conditions - Haiqian Zhao; Ziyu Tang; Zhonghua Wang; Jun Li; Zhipei Hu; Qingshu Wang; Qi Yu; Xing Zhang; Bo Zhou; Erlin Meng (Environmental Pollution, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Phytosphingosine inhibits the growth of lung adenocarcinoma cells by inducing G2/M-phase arrest, apoptosis, and mitochondria-dependent pathway cell death in vitro and in vivo - Qi Cai; Min Chen; Bo Wang; Jin Wang; Lijie Xia; Jinyao Li (Chemico-Biological Interactions, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

Establishment of a tilapia lake virus (TiLV)-susceptible cell line for anti-TiLV Chinese herbal compound screening - Song Zhu; Bo Miao; Yu-Zhou Zhang; Qin Yang; Xun-Teng Deng; Li-Hong Gao; Ji-Shu Zheng; De-Cheng Pu; De-Shou Wang; Sheng-Qi Su (Aquaculture, 2023)

A pilot study of situ sludge fermentation-driven multiple biological nitrogen removal pathways (SFBNR): Revealing microbial synergy mechanism based on co-occurrence network analysis - Xuepeng Fan; Li Zhang; Shuang Lan; Bo Wang; Weikang Qi; Yuchao Wu; Yongzhen Peng (Water Research, 2023)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

LC-MS-based untargeted metabolomics reveals the mechanism underlying prostate damage in a type 2 diabetes mouse model - Rong Qi; Shao-san Kang; Yongchao Pei; Mingming Liu; Yufan Zhou; Bo Guan; Xinduo Zhang; Zhiguo Li; Fenghong Cao (Reproductive Biology, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Dibutyl phthalate induces liver fibrosis via p38MAPK/NF-κB/NLRP3-mediated pyroptosis - Siming Huo; Bo Li; Jiayu Du; Xuliang Zhang; Jian Zhang; Qi Wang; Miao Song; Yanfei Li (Science of The Total Environment, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Propeller-shaft-hull coupling acoustic radiation characteristics induced by friction self-excitation of the stern bearing - Chang-Gang Lin; Ming-Song Zou; Li-Bo Qi; Can Sima; Ji-Long Chu (Ocean Engineering, 2023)

HVT-vectored H7 vaccine protects chickens from lethal infection with the highly pathogenic H7N9 Avian inﬂuenza virus - Yi-qun Chen; Guan-ming Su; Jia-hao Zhang; Bo Li; Kai-xiong Ma; Xu Zhang; Li-hong Huang; Ming Liao; Wen-bao Qi (Veterinary Microbiology, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Zircon xenocryst geochronology and implications for the Lhasa terrane evolution: Insights from Cenozoic volcanic rocks (Coqen, Tibet) - Yu-Fei Zhang; Bo Xu; Zeng-Qian Hou; Yi Zhao; Zi-Xuan Wang; Jia-Qi Shen; Guan-Yu Kou; Jia-Xing Yu; En-Qi Li (Journal of Asian Earth Sciences, 2023)

N-doped carbon dots coupled with molecularly imprinted polymers as a fluorescent sensor for ultrasensitive detection of genistein in soya products - Yu-Zhen Zhang; Bo Zhang; Qing-Qing Chen; Lan Qin; Ya-Qi Hu; Chun-Hua Bai; Yi-Le Li; Bei Qin (Food Chemistry, 2023)

Biochar-supported Fe3C nanoparticles with enhanced interfacial contact as high-performance binder-free anode material for microbial fuel cells - Bo Song; Qi Wang; Jafar Ali; Zhibin Wang; Lei Wang; Jiahe Wang; Jiaxin Li; Evgeni M. Glebov; Xuliang Zhuang (Chemical Engineering Journal, 2023)

Wuzi Yanzong Pill relieves MPTP-induced motor dysfunction and neuron loss by inhibiting NLRP3 inflammasome-mediated neuroinflammation - Tao Pan; Qi Xiao; Hui-Jie Fan; Lei Xu; Shao-Chen Qin; Li-Xia Yang; Xiao-ming Jin; Bao-Guo Xiao; Bo Zhang; Cun-Gen Ma; Zhi Chai (Metabolic Brain Disease, 2023)

Dibutyl phthalate causes heart damage by disrupting Ca2+ transfer from endoplasmic reticulum to mitochondria and triggering subsequent pyroptosis - Bo Li; Siming Huo; Jiayu Du; Xuliang Zhang; Jian Zhang; Qi Wang; Miao Song; Yanfei Li (Science of The Total Environment, 2023)

Multi-scale coupling numerical modeling of metallic strip flexible pipe during reel-lay process - Weidong Ruan; Kefu Qi; Xiangxi Han; Bo Sun; Xiaofeng Gao; Jiantao Li (Ocean Engineering, 2023)

Analysis of energy, exergy and CO2 emissions in a fiberglass furnace with oxy-fuel combustion - Yuan Yao; Jun-yao He; Qi Chen; Teng Li; Bo Li; Xiao-lin Wei (Fuel, 2023)

Donor-Acceptor molecule with TICT character: a new design strategy for organic photothermal material in solar energy - Jianan Dai; Shuo Qi; Meng Zhao; Jing Liu; Tao Jia; Guannan Liu; Fangmeng Liu; Peng Sun; Bo Li; Chenguang Wang; Ji Zhou; Geyu Lu (Chemical Engineering Journal, 2023)

Gypenosides suppress hepatocellular carcinoma cells by blocking cholesterol biosynthesis through inhibition of MVA pathway enzyme HMGCS1 - Man-Yu Xiao; Fang-Fang Li; Peng Xie; Yan-Shuang Qi; Jin-Bo Xie; Wen-Jing Pei; Hao-Tian Luo; Mei Guo; Yu-Long Gu; Xiang-Lan Piao (Chemico-Biological Interactions, 2023)

Improved biotransformation of lignin-valorized vanillin into vanillylamine in a sustainable bioreaction medium - Qi Li; Ruiying Gao; Yucheng Li; Bo Fan; Cuiluan Ma; Yu-Cai He (Bioresource Technology, 2023)

Highly sensitive detection of microRNA-21 by nitrogen-doped carbon dots-based ratio fluorescent probe via nuclease-assisted rolling circle amplification strategy - Shan Huang; Bo Li; Pingping Mu; Wenqian Zhang; Yi Liu; Qi Xiao (Analytica Chimica Acta, 2023)

Modelling water/heat transfer and crop growth under film mulching condition in a seed–maize field - Yin Zhao; Xiaomin Mao; Manoj K. Shukla; Sien Li; Zunqiu Xu; Liyuan Bo; Xi Huang; Yuting Bai; Xingchao Qi (Agricultural and Forest Meteorology, 2023)

The induction of ferroptosis by KLF11/NCOA4 axis: the inhibitory role in clear cell renal cell carcinoma - Zi-Qi Zhou; Xi Lv; Shi-Bo Liu; Hong-Chen Qu; Qing-Peng Xie; Long-Feng Sun; Gang Li (Human Cell, 2023)

Syringin alleviates hepatic fibrosis by enhancing autophagic flux and attenuating ER stress-TRIB3/SMAD3 in diabetic mice - Zhewen Deng; Chaoxing Ren; Chenglun Tang; Shuang Chen; Jiaqi Li; Jingxun Wei; Qi Zhang; Bo Ma (Tissue and Cell, 2023)

Synthesis of novel magnetic pitch-based hypercrosslinked polymers as adsorbents for effective recovery of Ag+ with high selectivity - Qi Peng; Hongwei Zhao; Guang Chen; Qilin Yang; Xinxiu Cao; Shaohui Xiong; Anguo Xiao; Gen Li; Bo Liu; Qingquan Liu (Journal of Environmental Management, 2023)

Necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage - Jiayu Du; Xuliang Zhang; Jian Zhang; Siming Huo; Bo Li; Qi Wang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2023)

A study on the analysis of dynamical transmission behavior and mining key monitoring stations in PM and O3 networks in the Beijing-Tianjin-Hebei region of China - Xiaofei Shi; Bo Li; Donglei Fu; Jiao Bai; Stephen Dauda Yabo; Kun Wang; Xiaoxiao Gao; Jie Ding; Hong Qi (Environmental Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Effect of humic acid-modified attapulgite on polycyclic aromatic hydrocarbon adsorption and release from paddy soil into the overlying water in a rice-crab coculture paddy ecosystem and the underlying process - Nan Sun; Jin Liu; Bo-Wei Qi; Li-Li Lu; Hui-Ling Du; Shuang Li; Chang-Qing Li; Si-Wen Jiang; Zi-Jian Wang; An-Pei Yang; Guang-Lei Zhu; Tian-Yi Wang; et al. (Chemosphere, 2023)

A novel membrane-based integrated process for baicalin recovery from TCM Pudilan wastewater - Xianli Zhang; Ruixiang Ying; Xuanru Chen; Qi Li; Jinhui Xu; Jiaoyue Qiu; Yanan Kong; Yue Zhang; Jianguo Shao; Fagen Zhu; Jinao Duan; Zhishu Tang; et al. (Journal of Water Process Engineering, 2023)

Occurrence, distribution, and risk assessment of quinolone antibiotics in municipal sewage sludges throughout China - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Hazardous Materials, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

Synergistic effect of lecithin and alginate, CMC, or PVP in stabilizing curcumin and its potential mechanism - Wo-Qi Cai; Xuanling Liu; Wenting Chen; Zijie Huang; Chendong Li; Xianru Huang; Corke Harold; Bao-Lian Su; Bo-Bo Zhang; Qiong-Qiong Yang (Food Chemistry, 2023)

The contrasting effects of fluctuating temperature on bacterial diversity and performances in temperate and subtropical soils - Xin‐Feng Zhao; Bo‐Hui Li; Wen‐Sheng Shu; Yi‐Qi Hao (Molecular Ecology, 2023)
The extremely high species diversity of soil bacterial community has fascinated and puzzled community ecologists. Although theory predicts that fluctuations in environments can facilitate diversity maintenance, the effects of fluctuating temperature on species diversity have rarely been investigated in species‐rich microbial communities. Here, we examined whether fluctuating temperature had positive effects on species diversity relative to constant temperatures in soil bacterial communities, and investigated the effects of fluctuating temperature on bacterial performances (changes in relative abundance). We performed a temperature manipulation experiment with soils collected from temperate and subtropical zones, where the soils were subjected to constant high, low or fluctuating temperatures. We found that fluctuating temperatures showed significant positive effects on species diversity. The time‐averaged effect of fluctuating temperatures (i.e., averaging out the differences between species in their environment‐dependent performances) appeared to delay species loss in both the temperate and the subtropical communities. In addition, we found that the performances of temperature‐responsive species at fluctuating temperatures significantly deviated from their time‐weighted average performances at constant high and low temperatures, which was defined as fluctuation‐dependent effects in our study. Intriguingly, fluctuation‐dependent effects beyond time‐averaged effect led to an opposite trend: differences in temperature‐responsive species' performances decreased in the temperate communities, but increased in the subtropical communities. Our findings provide new insights into diversity maintenance in soil bacterial communities, and imply that the effects of fluctuating temperature on species diversity in soil bacterial community might vary across latitude.

Recent developments in the application of membrane separation technology and its challenges in oil-water separation: A review - Bingfan Li; Bo Qi; Ziyuan Guo; Dongxu Wang; Tifeng Jiao (Chemosphere, 2023)

In-situ anaerobic treatment removes the passivation layer of sponge iron to restore the nitrogen and phosphorus removal performance of SBR - Kaiyao Hu; Wenxuan Li; Hao Mu; Shuang Ren; Hongjuan Zhu; Kexin Zeng; Bo Wang; Jinming Liang; Qi Zhang; Lili Yang; Wei Zhao; Juqiang Xiao (Process Safety and Environmental Protection, 2023)

Aconicumines A–D, an advanced class of norditerpenoid alkaloids with an unprecedented N,O-diacetal motif from Aconitum taipeicum Hand.-Mazz., exhibit anti-inflammatory properties in vitro - Dong-Bo Zhang; Yan-Ni Liang; Zheng Wang; Li-Ke Shi; Zhen Zhang; Zhi-Shu Tang; Lu-Qi Huang (Phytochemistry, 2023)

Asphaltene dispersants weaken the synergistic modification effect of ethylene-vinyl acetate and asphaltene for model waxy oil - Xue Xia; Chuanxian Li; Yujia Qi; Huimin Shi; Guangyu Sun; Bo Yao; Fei Yang; Yansong Zhao (Fuel, 2023)

Micro and nanobubbles technologies as a new horizon for CO2-EOR and CO2 geological storage techniques: A review - Xiaofeng Li; Bo Peng; Qi Liu; Jianwei Liu; Leiwang Shang (Fuel, 2023)

Discovery of seven-membered ring berberine analogues as highly potent and specific hCES2A inhibitors - Yun Yang; Yuan Xiong; Guanghao Zhu; Mengru Sun; Kun Zou; Yitian Zhao; Yong Zhang; Zhijian Xu; Yiming Li; Weiliang Zhu; Qi Jia; Bo Li; et al. (Chemico-Biological Interactions, 2023)

Internet addiction-induced brain structure and function alterations: a systematic review and meta-analysis of voxel-based morphometry and resting-state functional connectivity studies - Jing-Ting Sun; Bo Hu; Tian-Qi Chen; Zhu-Hong Chen; Yu-Xuan Shang; Yu-Ting Li; Rui Wang; Wen Wang (Brain Imaging and Behavior, 2023)

Magnesium Ions Promote In Vitro Rat Bone Marrow Stromal Cell Angiogenesis Through Notch Signaling - Haotian Qin; Jian Weng; Bo Zhou; Weifei Zhang; Guoqing Li; Yingqi Chen; Tiantian Qi; Yuanchao Zhu; Fei Yu; Hui Zeng (Biological Trace Element Research, 2023)

Casing deformation risk assessment method based on fault–slip theory and its application to shale formations - Jun-Chuan Gui; Yu Sang; Bo Zeng; Hao-Yong Huang; Qi-Yong Gou; Jun-Feng Li; Er-Si Xu; Guang-Hai Zhong (Applied Geophysics, 2023)

Effects of Bacillus strain added as initial indigenous species into the biofloc system rearing Litopenaeus vannamei juveniles on biofloc preformation, water quality and shrimp growth - Hai-Hong Huang; Chao-Yun Li; Yan-Ju Lei; Bo-Lan Zhou; Wei-Qi Kuang; Wan-Sheng Zou; Pin-Hong Yang (Aquaculture, 2023)

An integrated electrolysis-microfiltration-ion exchange closed-loop system for effective water softening without chemicals input and spent regenerant discharge - Xuchen Ba; Jinghua Chen; Xuesong Wang; Hao Xu; Junqiang Sun; Yuanfeng Qi; Yifan Li; Juan Wang; Bo Jiang (Desalination, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Biodegradation of isobutyraldehyde with high removal efficiency by using a modified biotrickling filter - Tao Gu; Yunhui Li; Qingdian Yin; Chun Miao; Bo Zhang; Zhiyong Xie; Kang Wang; Shengping You; Wei Qi; Rongxin Su (Journal of Environmental Chemical Engineering, 2023)

Understanding the inter-city causality and regional transport of atmospheric PM2.5 pollution in winter in the Harbin-Changchun megalopolis in China: A perspective from local and regional - Bo Li; Xiaofei Shi; Jinpan Jiang; Lu Lu; Li-xin Ma; Wei Zhang; Kun Wang; Hong Qi (Environmental Research, 2023)

Natural Polyphenol-Inspired Polymer towards Multifunction and High Performance - Guan-Qi Zheng; Bo-Wen Liu; Ling Yuan; Lin Chen; Xiu-Li Wang; Hai-Bo Zhao; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Biodegradable, anti-freezing and self-healable hydrogel mulch film for weed control - Shan-Shan Li; Song-Bo Wang; Yu Chen; Qi-Shun Zhu; Ling-Min Lan; Huaitian Bu; Tian Hu; Gang-Biao Jiang (Chemical Engineering Journal, 2023)

Unraveling the contribution of valence state to the NO oxidation activity of manganese oxides - Zhiyu Qi; Bo Chen; Baochang Man; Zhengwen Li; Kai Feng; Binhang Yan; Guohua Luo (Chemical Engineering Journal, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

Drivers of 2015–2021 trends in cold winter surface PM2.5 in the Harbin-Changchun megalopolis in China: Meteorology vs. anthropogenic emission - Bo Li; Lu Lu; Xiaofei Shi; Lixin Ma; Jin-Pan Jiang; Stephen Dauda Yabo; Kun Wang; Hong Qi (Atmospheric Research, 2023)

Comparative transcriptomics and co-expression networks reveal cultivar-specific molecular signatures associated with reproductive-stage cold stress in rice - Yuan Niu; Song Fan; Baoshan Cheng; Henan Li; Jiang Wu; Hongliang Zhao; Zhiwei Huang; Feiyu Yan; Bo Qi; Linqing Zhang; Guoliang Zhang (Plant Cell Reports, 2023)

The infertile individual analysis based on whole-exome sequencing in chinese multi-ethnic groups - Qiongzhen Zhao; Yanqi Li; Qi Liang; Jie Zhao; Kai Kang; Meiling Hou; Xin Zhang; Renqian Du; Lingyin Kong; Bo Liang; Weidong Huang (Genes & Genomics, 2023)

Synergistic interactions of fine particles and radiative effects in modulating urban heat islands during winter haze event in a cold megacity of Northeast China - Stephen Dauda Yabo; Donglei Fu; Bo Li; Lixin Ma; Xiaofei Shi; Lu Lu; Xie Shengjin; Fan Meng; Jinpan Jiang; Wei Zhang; Hong Qi (Environmental Science and Pollution Research, 2023)

Effect of feeding level on growth, digestive and metabolic enzymes and antioxidant capacity in juvenile Yangtze sturgeon (Acipenser dabryanus) - Bin He; Bo Zhou; Hang Xie; Zeng-Tan Hu; Bin Wang; Jun-Lin Zhang; Qing-Zhi Li; Feng-Qi Zhao; Xing Liu; Qian-Dong Li; Tao Yan (Aquaculture, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Automatic detection of river capture based on planform pattern and χ-plot of the stream network - Qi-Yuan Ma; An-Bo Li; Ping Wang (Geomorphology, 2023)

The combined effects of NaCl-pH and urea-pH on the phase separation of type-A gelatin and dextran - Qi Wang; Bo Cui; Li Guo; Zhao Li; Qingqing Chai; Na Wang; Die Dong; Katsuyoshi Nishinari; Meng Zhao (Food Hydrocolloids, 2023)

Unraveling the antibacterial mechanism of Lactiplantibacillus plantarum MY2 cell-free supernatants against Aeromonas hydrophila ST3 and potential application in raw tuna - Di Wang; Yangfan Liu; Xupeng Li; Shengjun Chen; Jianchao Deng; Chunsheng Li; Chuang Pan; Yueqi Wang; Huan Xiang; Yang Feng; Xianqing Yang; Laihao Li; et al. (Food Control, 2023)

Why did air quality experience little improvement during the COVID-19 lockdown in megacities, northeast China? - Donglei Fu; Xiaofei Shi; Jinxiang Zuo; Stephen Dauda Yabo; Jixiang Li; Bo Li; Haizhi Li; Lu Lu; Bo Tang; Hong Qi; Jianmin Ma (Environmental Research, 2023)

Purinergic signaling: a potential therapeutic target for ischemic stroke - Lu Wang; Ying-Jie Li; Xu Yang; Bo Yang; Xin Zhang; Jing Zhang; Qi Zhang; Xu-Dong Cheng; Jian-Hong Wang; Neng-Wei Yu (Purinergic Signalling, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Inhibition of perilipin 2 attenuates cerebral ischemia/reperfusion injury by blocking NLRP3 inflammasome activation both in vivo and in vitro - Xu-Ying Liu; Qiu-Shi Li; Wen-Hai Yang; Yue Qiu; Fei-Fei Zhang; Xiu-Hui Mei; Qi-Wen Yuan; Ru-Bo Sui (In Vitro Cellular & Developmental Biology - Animal, 2023)

Empirical seismic vulnerability assessment model of typical urban buildings - Si-Qi Li; Yong-Sheng Chen; Hong-Bo Liu; Carlo Del Gaudio (Bulletin of Earthquake Engineering, 2023)

Noval bio-organic fertilizer containing Arthrobacter sp. DNS10 alleviates atrazine-induced growth inhibition on soybean by improving atrazine removal and nitrogen accumulation - Zhao Jiang; Qi Shao; Yu Li; Bo Cao; Jin Li; Zheyi Ren; Jianhua Qu; Ying Zhang (Chemosphere, 2023)

Interaction of Scenedesmus quadricauda and native bacteria in marine biopharmaceutical wastewater for desirable lipid production and wastewater treatment - Junren Chen; Zian Ren; Zheng Li; Bo Wang; Yuejun Qi; Wenbao Yan; Qingqing Liu; Hengyu Song; Qingxiang Han; Lijie Zhang (Chemosphere, 2023)

Identification and pathogenetic study of tilapia lake virus (TiLV) isolated from naturally diseased tilapia - Tao He; Yu-Zhou Zhang; Li-Hong Gao; Bo Miao; Ji-Shu Zheng; De-Cheng Pu; Qing-Qing Zhang; Wei-Wei Zeng; De-Shou Wang; Sheng-Qi Su; Song Zhu (Aquaculture, 2023)

A Late Jurassic magmatic flare-up triggered by break-off of the Bangong-Nujiang Meso-Tethyan slab: Insights from Jurassic arc magmatism in South Qiangtang, Central Tibet - Neng Gong; Hui Qi; Jun Li; Guo-Li Yuan; Gen-Hou Wang; Xiao Liang; Zhi-Bo Liu (Lithos, 2023)

Comprehensive application possibility: Construction hydrophilic, amphiphilic and hydrophobic system of modified zein by enzymatic or cysteine modification - An-Qi Zhang; Xiao-Yan Li; Bo-Hao Liu; Yu-Qi Yin; Han-Lin Zhang; Ying-Hua Zhang (Food Hydrocolloids, 2023)

Experiment and numerical simulation study of dynamic mechanical behavior of granite specimen after high temperature treatment - Sheng-Qi Yang; Ye Li; Guo-Wei Ma; Bo-Wen Sun; Jing Yang; Jie Xu; Yong-Hao Dai (Computers and Geotechnics, 2023)

Dual sites design of CoFe/Mg MMO catalyst for effectively suppressing dimethylamine re-emission: Degradation products and DFT calculation - Lin Zhang; Juanjuan Qi; Haiyang Zhang; Lei Xing; Zhanqi Zhou; Renchan Lei; Bo Li; Hui Liu; Lidong Wang (Chemical Engineering Journal, 2023)

Mimicking the competitive interactions to reduce resistance induction in antibacterial actions - Shuo Zhao; Zheyu Li; Suyao Yin; Qi-dai Chen; Hong-bo Sun; Liping Wen; Lei Jiang; Kai Sun (Chemical Engineering Journal, 2023)

Stabilized effects of L-S cement-mixed batter pile composite foundation for existed warm frozen soil subgrade - Gao-chen Sun; Gang Yao; Jian-ming Zhang; Bo Li; Jun-qi Li; Wei-ping Lian; Yi Wei (Journal of Mountain Science, 2023)

Catalytic pyrolysis of spent bleaching clay for its regeneration and simultaneously producing aromatic hydrocarbons - Kai Li; Zhu-yu Li; Cheng-Bo Zhang; Jia-qi Zhao; Li Zhao; Ji Liu; Shan-wei Ma; Qiang Lu (Journal of Cleaner Production, 2023)

The source distribution and seasonal discrepancies of antibiotic resistance genes among multiple environment media in a cold megacity - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Cleaner Production, 2023)

The pH-dependent phase separation kinetics of type-A gelatin and dextran with different initial microstructures - Qi Wang; Zhongqiu Han; Bo Cui; Chao Yuan; Jianpeng Li; Katsuyoshi Nishinari; Meng Zhao (Food Hydrocolloids, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

Recent progress of hollow structure platform in assisting oxygen evolution reaction - Qiaoli Li; Fengmin Sun; Di Zhang; Huilan Sun; Qiujun Wang; Jian Qi; Huan Wang; Zhaojin Li; Zhilin Hu; Bo Wang (Chemical Engineering Journal, 2023)

A novel partially carbonized Fe3O4@PANI-p catalyst for tetracycline degradation via peroxymonosulfate activation - Ya-qi Wang; Kun Li; Mao-yuan Shang; Yi-zhen Zhang; Yang Zhang; Bo-lai Li; Yu-jiao Kan; Xiao-qiang Cao; Jian Zhang (Chemical Engineering Journal, 2023)

Corrigendum to “CD44-targeted hyaluronic acid-curcumin prodrug protects renal tubular epithelial cell survival from oxidative stress damage” [Carbohydrate Polymers 193 (2018) 268–280] - Jing-Bo Hu; Shu-Juan Li; Xu-Qi Kang; Jing Qi; Jia-Hui Wu; Xiao-Juan Wang; Xiao-Ling Xu; Xiao-Ying Ying; Sai-Ping Jiang; Jian You; Yong-Zhong Du (Carbohydrate Polymers, 2023)

An Acid-triggered Reactive and Enhanced Fluorescent Probe for Selective Detection of Al3+/H+ and its Application in Real Water Samples and Living Cells - Zhigang Li; Bing Zhao; Wei Kan; Fanqiang Bu; Xin Qi; Liyan Wang; Bo Song; Limin Ding (Journal of Fluorescence, 2023)

Low-Level Environmental Per- and Polyfluoroalkyl Substances and Preterm Birth: A Nested Case–Control Study Among a Uyghur Population in Northwestern China - Bo-Yi Yang; Jianhua Wu; Xilong Niu; Chuanjiang He; Michael S. Bloom; Maihefuzaimu Abudoukade; Mairiyemu Abulizi; Aimin Xu; Beibei Li; Li Li; Xuemei Zhong; Qi-Zhen Wu; et al. (Exposure and Health, 2022)

Mitigation of atrazine-induced oxidative stress on soybean seedlings after co-inoculation with atrazine-degrading bacterium Arthrobacter sp. DNS10 and inorganic phosphorus-solubilizing bacterium Enterobacter sp. P1 - Zhao Jiang; Qi Shao; Yuxin Chu; Ning An; Bo Cao; Zheyi Ren; Jin Li; Jianhua Qu; Maofeng Dong; Ying Zhang (Environmental Science and Pollution Research, 2022)

Toluene degradation using plasma-catalytic hybrid system over Mn-TiO2 and Fe-TiO2 - Li-qiang Qi; Zhe Yu; Qi-hao Chen; Jing-xin Li; Hao-bo Xue; Feng Liu (Environmental Science and Pollution Research, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Cumulative risk assessment of dietary exposure to phthalates in pregnant women in Beijing, China - Danping Shan; Tao Zhang; Ludi Li; Yuqing Sun; Di Wang; Yingzi Li; Zheng Yang; Kanglong Cui; Shaowei Wu; Lei Jin; Bo Hong; Xuejun Shang; et al. (Environmental Science and Pollution Research, 2022)

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

Dual-specificity Tyrosine Phosphorylation-regulated Kinase Inhibitor ID-8 Promotes Human Somatic Cell Reprogramming by Activating PDK4 Expression - Jinhong Xu; Shi Fang; Naweng Wang; Bo Li; Yongheng Huang; Qi Fan; Jingyi Shi; Huihui Liu; Zhicheng Shao (Stem Cell Reviews and Reports, 2022)

Uncertainties in Prediction of Near-Fault Long-Period Ground Motion: An Application to the 1970 Tonghai Earthquake (Ms 7.8) - Zhiwei Ji; Zongchao Li; Xueliang Chen; Tiefei Li; Qing Wu; Bo Zhang; Qi Li; Ting Huang (Pure and Applied Geophysics, 2022)

Vulnerability prediction model of typical structures considering empirical seismic damage observation data - Si-Qi Li; Hong-Bo Liu (Bulletin of Earthquake Engineering, 2022)

Nematicidal activity of volatile organic compounds produced by Bacillus altitudinis AMCC 1040 against Meloidogyne incognita - Lin Ye; Jian-Yu Wang; Xiao-Fang Liu; Qi Guan; Nong-Xiao Dou; Jian Li; Qian Zhang; Yan-Ming Gao; Min Wang; Jian-She Li; Bo Zhou (Archives of Microbiology, 2022)

Glycosides from Buddleja officinalis with their protective effects on photoreceptor cells in light-damaged mouse retinas - Zehai Long; Xiaoye Du; Qiyao Wang; Zhijian Xu; Bo Li; Yong Zhang; Yu Chen; Qi Jia; Yiming Li; Weiliang Zhu (Natural Product Research, 2022)

Clinical Reference Strategy for the Selection of Treatment Materials for Maxillofacial Bone Transplantation: A Systematic Review and Network Meta-Analysis - Shuxin Zhang; Xinyi Zhang; Yanli Li; Xuran Mao; Rui Liu; Yanxin Qi; Eui-Seok Lee; Heng Bo Jiang (Tissue Engineering and Regenerative Medicine, 2022)

LncDACH1 promotes mitochondrial oxidative stress of cardiomyocytes by interacting with sirtuin3 and aggravates diabetic cardiomyopathy - Qi Zhang; Danyang Li; Xue Dong; Xiaowen Zhang; Junwu Liu; Lili Peng; Bo Meng; Qi Hua; Xinyu Pei; Lu Zhao; Xiaoxi Hu; Yang Zhang; et al. (Science China Life Sciences, 2022)

Considering economic-environmental joint benefits of water-land resources allocation for supporting sustainable agricultural system development in northeastern China - Yongyang Wang; Yulei Xie; Yanpeng Cai; Gengyuan Liu; Pan Zhang; Bowen Li; Bo Li; Qunpo Jia; Zixuan Qi; Jin Zhang (Environmental Science and Pollution Research, 2022)

Impact of land cover transformation on urban heat islands in Harbin, China - Stephen Dauda Yabo; Donglei Fu; Bo Li; Xiaofei Shi; Samit Thapa; Xie Shengjin; Lu Lu; Hong Qi; Wei Zhang (Environmental Monitoring and Assessment, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Alpine vegetation responses to snow phenology in the Chinese Tianshan mountainous region - Bo Zhang; Xue-mei Li; Chao Li; Christine Nyiransengiyumva; Qi-yong Qin (Journal of Mountain Science, 2022)

A novel microRNA regulates cooperation between symbiont and a laterally acquired gene in the regulation of pantothenate biosynthesis within Bemisia tabaci whiteflies - Xiang Sun; Bing‐Qi Liu; Chu‐Qiao Li; Zhan‐Bo Chen; Xiao‐Rui Xu; Jun‐Bo Luan (Molecular Ecology, 2022)
Horizontally transferred genes (HTGs) play a key role in animal symbiosis, and some horizontally transferred genes or proteins are highly expressed in specialized host cells (bacteriocytes). However, it is not clear how HTGs are regulated, but microRNAs (miRNAs) are prime candidates given their previously demonstrated roles in symbiosis and impacts on the expression of host genes. A horizontally acquired PanBC that is highly expressed in whitefly bacteriocytes can cooperate with an obligate symbiont Portiera for pantothenate production, facilitating whitefly performance and Portiera titre. Here, we found that a whitefly miRNA, novel‐m0780‐5p, was up‐regulated and its target panBC was down‐regulated in Portiera ‐eliminated whiteflies. This miRNA was located in the cytoplasmic region of whitefly bacteriocytes. Injection of novel‐m0780‐5p agomir reduced the expression of PanBC in whitefly bacteriocytes, while injection of novel‐m0780‐5p antagomir enhanced PanBC expression. Agomir injection also reduced the pantothenate level, Portiera titre and whitefly performance. Supplementation with pantothenate restored Portiera titre and the fitness of agomir‐injected whiteflies. Thus, we demonstrate that a whitefly miRNA regulates panBC ‐mediated host–symbiont collaboration required for pantothenate synthesis, benefiting the whitefly– Portiera symbiosis. Both panBC and novel‐m0780‐5p are present in the genomes of six Bemisia tabaci species. The expression of a novel miRNA in multiple B . tabaci species suggests that the miRNA evolved after panBC acquisition, and allowed this gene to be more tightly regulated. Our discovery provides the first account of a HTG being regulated by a miRNA from the host genome, and suggests key roles for interactions between miRNAs and HTGs in the functioning of symbiosis.

Correction to: Downregulation of fibronectin 1 attenuates ATRA‑induced inhibition of cell migration and invasion in neuroblastoma cells - Xiaolin Tan; Wei Gong; Bo Chen; Baocheng Gong; Zhongyan Hua; Simeng Zhang; Yang Chen; Qi Li; Zhijie Li (Molecular and Cellular Biochemistry, 2022)

Recycling of supra-crustal materials in the rhyolites from north Sonid Youqi: implications for the crustal evolution in the southeast Central Asian Orogenic Belt - Jian-Zhou Tang; Zhicheng Zhang; Bo Liu; Shaohua Zhang; Ke Li; Qi Wang; Cong Ding (International Journal of Earth Sciences, 2022)

LncRNA Riken Attenuated Sevoflurane-Induced Neuroinflammation by Regulating the MicroRNA-101a/MKP-1/JNK Pathway - Qi Hou; Shuai Li; Bo Zhang; Huaqing Chu; Cheng Ni; Xuejie Fei; Hui Zheng (Neurotoxicity Research, 2022)

Systematic Input–Output Mapping Reveals Structural Plasticity of VTA Dopamine Neurons-Zona Incerta Loop Underlying the Social Buffering Effects in Learned Helplessness - Hongwei Cai; Pei Zhang; Guangjian Qi; Lijun Zhang; Tongxia Li; Ming Li; Xinyuan Lv; Jie Lei; Jie Ming; Bo Tian (Molecular Neurobiology, 2022)

The spatiotemporal distribution and potential risk assessment of 19 phthalate acid esters in wastewater treatment plants in China - Shaojing Sun; Jimin Shen; Bo Li; Jialu Geng; Lixin Ma; Hong Qi; Anping Zhang; Zebin Zhao (Environmental Science and Pollution Research, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Seismic Coherence for Discontinuity Interpretation - Fangyu Li; Bin Lyu; Jie Qi; Sumit Verma; Bo Zhang (Surveys in Geophysics, 2021)

Dopaminergic Projection from Ventral Tegmental Area to Substantia Nigra Pars Reticulata Mediates Chronic Social Defeat Stress–Induced Hypolocomotion - Feng He; Pei Zhang; Qian Zhang; Guangjian Qi; Hongwei Cai; Tongxia Li; Ming Li; Jiazhen Lu; Jiaen Lin; Jie Ming; Bo Tian (Molecular Neurobiology, 2021)

Downregulation of fibronectin 1 attenuates ATRA-induced inhibition of cell migration and invasion in neuroblastoma cells - Xiaolin Tan; Wei Gong; Bo Chen; Baocheng Gong; Zhongyan Hua; Simeng Zhang; Yang Chen; Qi Li; Zhijie Li (Molecular and Cellular Biochemistry, 2021)

Apigenin Improves Hypertension and Cardiac Hypertrophy Through Modulating NADPH Oxidase-Dependent ROS Generation and Cytokines in Hypothalamic Paraventricular Nucleus - Hong-Li Gao; Xiao-Jing Yu; Han-Bo Hu; Qian-Wen Yang; Kai-Li Liu; Yan-Mei Chen; Yan Zhang; Dong-Dong Zhang; Hua Tian; Guo-Qing Zhu; Jie Qi; Yu-Ming Kang (Cardiovascular Toxicology, 2021)

Assessment of the Nutritional Value of Cultured Sea Cucumber Apostichopus japonicus - Meng Li; Yue Gao; Yan-xia Qi; Zhi-yuan Song; Zhi-bo Li; Yan-tong Lin; Qian-cheng Zhao (Journal of Aquatic Food Product Technology, 2021)

Impact of climate change on snowmelt runoff in a Himalayan basin, Nepal - Samit Thapa; Haizhi Li; Bo Li; Donglei Fu; Xiaofei Shi; Stephen Yabo; Lu Lu; Hong Qi; Wei Zhang (Environmental Monitoring and Assessment, 2021)

Comparison of Autogenous Tooth Materials and Other Bone Grafts - Shuxin Zhang; Xuehan Li; Yanxin Qi; Xiaoqian Ma; Shuzhan Qiao; HongXin Cai; Bing Cheng Zhao; Heng Bo Jiang; Eui-Seok Lee (Tissue Engineering and Regenerative Medicine, 2021)

Programmed sequential cutting endows Cas9 versatile base substitution capability in plants - Wei Yang; Wei Qi; Yucai Li; Jiyao Wang; Yanmin Luo; Dehui Ding; Sudong Mo; Bo Chen; Yu Lu; Huarong Li; Linjian Jiang (Science China Life Sciences, 2021)

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

Maternal Separation-Induced Histone Acetylation Correlates with BDNF-Programmed Synaptic Changes in an Animal Model of PTSD with Sex Differences - Haoran Sun; Xianqiang Zhang; Yujia Kong; Luping Gou; Bo Lian; Yanyu Wang; Li Jiang; Qi Li; Hongwei Sun; Lin Sun (Molecular Neurobiology, 2021)

In vitro Antioxidant Effects of Porphyra haitanensis Peptides on H2O2-Induced Damage in HepG2 Cells - Shengjun Chen; Jiao Yu; Xiao Hu; Xianqing Yang; Laihao Li; Bo Qi; Jianchao Deng (Journal of Ocean University of China, 2021)

Spatial distribution and ecological assessment of nickel in sediments of a typical small plateau lake from Yunnan Province, China - Bo Li; Hang Wang; Qingguo Yu; Feng Wei; Qi Zhang (Environmental Science and Pollution Research, 2021)

Neobacillus sedimentimangrovi sp. nov., a Thermophilic Bacterium Isolated from Mangrove Sediment - Rong Tang; Qi Zhang; Manik Prabhu Narsing Rao; Guo-Hong Liu; Jian-Mei Che; Min Lei; Bo Liu; Wen-Jun Li; Shun-Gui Zhou (Current Microbiology, 2021)

Network pharmacology uncovers anti-cancer activity of vibsane-type diterpenes from Viburnum odoratissimum - Ying-Ying Zhang; Jing-Jie Chen; Dan-Qi Li; Yan- Zhang; Xiao-Bo Wang; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2021)

Identification of Pythium species as pathogens of garlic root rot - Bo Zhang; Yueli Zhang; Liguo Ma; Kai Qi; Peng Wang; Changsong Li; Junshan Qi (Journal of Plant Pathology, 2021)

Molecular evolution and pathogenicity of chicken anemia virus isolates in China - Yue Li; Nana Yan; Yongqiang Wang; Aijing Liu; Changjun Liu; Xingge Lan; Bo Yang; Yulong Gao; Honglei Gao; Xiaole Qi; Hongyu Cui; Kai Li; et al. (Archives of Virology, 2021)

Overtopping process and structural safety analyses of the earth-rock fill dam with a concrete core wall by using numerical simulations - Qi-dong Hou; Hai-bo Li; Yu-xiang Hu; Shun-chao Qi; Jia-wen Zhou (Arabian Journal of Geosciences, 2021)

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Geological Survey and Unstable Rock Block Movement Monitoring of a Post-Earthquake High Rock Slope Using Terrestrial Laser Scanning - Hai-bo Li; Shun-chao Qi; Xing-guo Yang; Xiao-wen Li; Jia-wen Zhou (Rock Mechanics and Rock Engineering, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Decylubiquinone suppresses breast cancer growth and metastasis by inhibiting angiogenesis via the ROS/p53/ BAI1 signaling pathway - Jinghua Cao; Xiaohua Liu; Yang Yang; Bo Wei; Qianming Li; Guanquan Mao; Yajun He; Yuanyuan Li; Lingyun Zheng; Qianqian Zhang; Jiangchao Li; Lijing Wang; et al. (Angiogenesis, 2020)

Characterization of viromes within mosquito species in China - Jiang Du; Fan Li; Yelin Han; Shihong Fu; Bo Liu; Nan Shao; Haoxiang Su; Weijia Zhang; Dandan Zheng; Wenwen Lei; Jie Dong; Lilian Sun; et al. (Science China Life Sciences, 2020)

Trend analysis of climatic variables and their relation to snow cover and water availability in the Central Himalayas: a case study of Langtang Basin, Nepal - Samit Thapa; Bo Li; Donglei Fu; Xiaofei Shi; Bo Tang; Hong Qi; Kun Wang (Theoretical and Applied Climatology, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

The basic helix-loop-helix transcription factor OsBLR1 regulates leaf angle in rice via brassinosteroid signalling - Kun Wang; Meng-qi Li; Yan-peng Chang; Bo Zhang; Quan-zhi Zhao; Wen-li Zhao (Plant Molecular Biology, 2020)

Synchrotron Radiation-Based Three-Dimensional Visualization of Angioarchitectural Remodeling in Hippocampus of Epileptic Rats - Pan Gu; Zi-Hao Xu; Yu-Ze Cao; Sheng-Hui Liao; Qian-Fang Deng; Xian-Zhen Yin; Zhuo-Lu Wang; Zhuo-Hui Chen; Xin-Hang Hu; Hui Wang; Li-Zhi Li; Shi-Xin Liu; et al. (Neuroscience Bulletin, 2020)

Correction to: Limb Remote Ischemic Preconditioning Reduces Repeated Ketamine Exposure-Induced Adverse Effects in the Developing Brain of Rats - Ying Liu; An Qi Li; Wan Ma; Yu Bo Gao; Li Qin Deng; Chun Zhang; Jin Hai Meng (Journal of Molecular Neuroscience, 2020)

α-Arbutin Protects Against Parkinson’s Disease-Associated Mitochondrial Dysfunction In Vitro and In Vivo - Yaqi Ding; Deqin Kong; Tong Zhou; Nai-di Yang; Chenqi Xin; Jiajia Xu; Qi Wang; Hang Zhang; Qiong Wu; Xiaomei Lu; Kahleong Lim; Bo Ma; et al. (NeuroMolecular Medicine, 2020)

Numerical Investigation of the Semi-Active Flapping Foil of the Wave Glider - Zhanfeng Qi; Bo Zou; Huiqiang Lu; Jian Shi; Guofu Li; Yufeng Qin; Jingsheng Zhai (Journal of Marine Science and Engineering, 2019)
A numerical investigation is conducted to study the propulsive performance of the semi-active flapping foil of the wave glider, where the heaving smotion is fully prescribed, and the pitching motion is determined by the hydrodynamic force and torsion spring. A mesh for two-dimensional NACA0012 foil with the Reynolds number Re = 42000 is produced, and a dynamic mesh and sliding interface are used in the computation. The influences of reduced frequency, spring stiffness, and critical pitching amplitude on the hydrodynamic characteristics of semi-active flapping foil are systematically investigated. We find that there is a critical reduced frequency: When the reduced frequency is lower than the critical value, the propulsive performance of flapping foil can be improved exponentially, and when the reduced frequency is higher than the critical value, the semi-active flapping foil cannot provide an effective thrust. For a greater reduced frequency, there is an optimal spring stiffness value, which corresponds to the maximum value of the output power coefficient. For a lower reduced frequency, the mean value of the output power coefficient monotonically decreases as the spring stiffness increases. We also notice that the propulsive efficiency of flapping foil monotonically decreases as the spring stiffness increases. Finally, we find that the appropriate critical pitching amplitude can improve the propulsive performance of semi-active flapping foil, especially for greater heaving amplitudes.

Biogas production from anaerobic co-digestion of waste activated sludge: co-substrates and influencing parameters - Qi Yang; Bo Wu; Fubing Yao; Li He; Fei Chen; Yinghao Ma; Xiaoyu Shu; Kunjie Hou; Dongbo Wang; Xiaoming Li (Reviews in Environmental Science and Bio/Technology, 2019)

Mass movement and formation process analysis of the two sequential landslide dam events in Jinsha River, Southwest China - Hai-bo Li; Shun-chao Qi; Hao Chen; Hai-mei Liao; Yi-fei Cui; Jia-wen Zhou (Landslides, 2019)

Integrating Multiple-Try DREAM(ZS) to Model-Based Bayesian Geoacoustic Inversion Applied to Seabed Backscattering Strength Measurements - Bo Zou; Zhanfeng Qi; Guangchao Hou; Zhaoxing Li; Xiaochen Yu; Jingsheng Zhai (Journal of Marine Science and Engineering, 2019)
The key to model-based Bayesian geoacoustic inversion is to solve the posterior probability distributions (PPDs) of parameters. In order to obtain PPDs more efficiently and accurately, the state-of-the-art Markov chain Monte Carlo (MCMC) method, multiple-try differential evolution adaptive Metropolis(ZS) (MT-DREAM(ZS)), is integrated to the inverse problem because of its excellent ability to fully explore the posterior space of parameters. The effective density fluid model (EDFM), which is derived from Biot–Stoll theory to approximate the poroelastic model, and the published field measurements of backscattering strength are adopted to implement the inversion. The results show that part of the parameters can be estimated close to the measured values, and the PPDs obtained by dual-frequency inversion are more concentrated than those of single-frequency inversion because of the use of more measured backscattering strength data. Otherwise, the comparison between the predicted backscattering strength of dual-frequency inversion results and Jackson’s prediction shows that the solutions of the inverse problem are not unique and may have multiple optimal values. Indeed, the difference between the two predictions is essentially the difference in the estimation of the contribution of volume scattering to the total scattering. Nevertheless, both results are reasonable due to the lack of measurement of volume scattering parameters, and the inversion results given by the posterior probabilities based on the limited measurements and the adopted model are still considered to be reliable.

A Novel Event Detection Model for Water Distribution Systems Based on Data-Driven Estimation and Support Vector Machine Classification - Xiang-Yun Zou; Yi-Li Lin; Bin Xu; Zi-Bo Guo; Sheng-Ji Xia; Tian-Yang Zhang; An-Qi Wang; Nai-Yun Gao (Water Resources Management, 2019)

Transcriptome-wide analysis to dissect the transcription factors orchestrating the phase change from vegetative to reproductive development in Larix kaempferi - Wei-Bo Xiang; Wan-Feng Li; Shou-Gong Zhang; Li-Wang Qi (Tree Genetics & Genomes, 2019)

Monitoring of displacement evolution during the pre-failure stage of a rock block using ground-based radar interferometry - Hai-bo Li; Xing-guo Yang; Hai-long Sun; Shun-chao Qi; Jia-wen Zhou (Landslides, 2019)

Cyclin-dependent kinase 5 regulates proliferation, migration, tyrosinase activity, and melanin production in B16-F10 melanoma cells via the essential regulator p-CREB - Xiuqing Li; Ruifang Wang; Junzhen Zhang; Shanshan Yang; Kaiyuan Ji; Bin Du; Xuexian Liu; Bo Liu; Shuhui Qi; Qiong Jia; Ruiwen Fan (In Vitro Cellular & Developmental Biology - Animal, 2019)

Biological perchlorate reduction: which electron donor we can choose? - Li He; Yu Zhong; Fubing Yao; Fei Chen; Ting Xie; Bo Wu; Kunjie Hou; Dongbo Wang; Xiaoming Li; Qi Yang (Environmental Science and Pollution Research, 2019)

Limb Remote Ischemic Preconditioning Reduces Repeated Ketamine Exposure-Induced Adverse Effects in the Developing Brain of Rats - Ying Liu; An Qi Li; Wan Ma; Yu Bo Gao; Li Qin Deng; Chun Zhang; Jin Hai Meng (Journal of Molecular Neuroscience, 2019)

OsCDC48/48E complex is required for plant survival in rice (Oryza sativa L.) - Lei Shi; Xiao-bo Zhang; Yong-feng Shi; Xia Xu; Yuqing He; Guosheng Shao; Qi-na Huang; Jian-li Wu (Plant Molecular Biology, 2019)

Polymorphism analyses of 19 STRs in Labrador Retriever population from China and its heterozygosity comparisons with other retriever breeds - Meng-Lei Wang; Xiao-Ye Jin; Xin Xiong; Jin-Long Yang; Jian-Ping Li; Qi Wang; Bo-Feng Zhu; Ya-Jun Deng (Molecular Biology Reports, 2019)

Assembly and dispersal history of continental blocks within the Altun-Qilian-North Qaidam mountain belt, NW China - Changlei Fu; Zhen Yan; Xianqing Guo; Manlan Niu; Bo Cao; Qi Wu; Xiucai Li; Zongqi Wang (International Geology Review, 2019)

Large deformation and failure mechanism analyses of Tangba high slope with a high-intensity and complex excavation process - Qi-dong Hou; Gao-jian Wu; Hai-bo Li; Gang Fan; Jia-wen Zhou (Journal of Mountain Science, 2019)

Genomic and transcriptomic insights into the survival of the subaerial cyanobacterium Nostoc flagelliforme in arid and exposed habitats - Jin‐Long Shang; Min Chen; Shengwei Hou; Tao Li; Yi‐Wen Yang; Qi Li; Hai‐Bo Jiang; Guo‐Zheng Dai; Zhong‐Chun Zhang; Wolfgang R. Hess; Bao‐Sheng Qiu (Environmental Microbiology, 2019)
Summary The cyanobacterium Nostoc flagelliforme is an extremophile that thrives under extraordinary desiccation and ultraviolet (UV) radiation conditions. To investigate its survival strategies, we performed whole‐genome sequencing of N. flagelliforme CCNUN1 and transcriptional profiling of its field populations upon rehydration in BG11 medium. The genome of N. flagelliforme is 10.23 Mb in size and contains 10 825 predicted protein‐encoding genes, making it one of the largest complete genomes of cyanobacteria reported to date. Comparative genomics analysis among 20 cyanobacterial strains revealed that genes related to DNA replication, recombination and repair had disproportionately high contributions to the genome expansion. The ability of N. flagelliforme to thrive under extreme abiotic stresses is supported by the acquisition of genes involved in the protection of photosynthetic apparatus, the formation of monounsaturated fatty acids, responses to UV radiation, and a peculiar role of ornithine metabolism. Transcriptome analysis revealed a distinct acclimation strategy to rehydration, including the strong constitutive expression of genes encoding photosystem I assembly factors and the involvement of post‐transcriptional control mechanisms of photosynthetic resuscitation. Our results provide insights into the adaptive mechanisms of subaerial cyanobacteria in their harsh habitats and have important implications to understand the evolutionary transition of cyanobacteria from aquatic environments to terrestrial ecosystems.

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Evaluation of Calcium Oxide of Quicklime and Si–Ca–Mg Fertilizer for Remediation of Cd Uptake in Rice Plants and Cd Mobilization in Two Typical Cd-Polluted Paddy Soils - Xin-Yang Li; Jian Long; Pei-Qin Peng; Qi Chen; Xia Dong; Kai Jiang; Hong-Bo Hou; Bo-Han Liao (International Journal of Environmental Research, 2018)

Enzymatic gene expression by Pleurotus tuoliensis (Bailinggu): differential regulation under low temperature induction conditions - Shuang Hua; Bo Zhang; Yongping Fu; Bao Qi; Yanshuang Li; Fenghua Tian; Yu Li (World Journal of Microbiology and Biotechnology, 2018)

Spatiotemporal characteristics of earthquake disaster losses in China from 1993 to 2016 - Xiaoli Li; Zhiqiang Li; Jiansi Yang; Yaohui Liu; Bo Fu; Wenhua Qi; Xiwei Fan (Natural Hazards, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Batesian insect-insect mimicry-related explosive radiation of ancient alienopterid cockroaches - Peter Vršanský; Günter Bechly; Qingqing Zhang; Edmund A. Jarzembowski; Tomáš Mlynský; Lucia Šmídová; Peter Barna; Matúš Kúdela; Danil Aristov; Sonia Bigalk; Lars Krogmann; Liqin Li; et al. (Biologia, 2018)

The complete mitochondrial genome of Pseudocrossocheilus bamaensis (Cypriniformes: Cyprinidae: Labeoninae) - Man Zhang; Bo-wen Liu; Guang-ping Cheng; Li Bian; Qi-jia Zhou; Wei-jie Yan; Wen-hong Li (Conservation Genetics Resources, 2018)

Recent Developments in Commercial Processes for Refining Bio-Feedstocks to Renewable Diesel - Bo Zhang; Jinsheng Wu; Changyan Yang; Qi Qiu; Qiangu Yan; Rui Li; Baowei Wang; Jinlong Wu; Yigang Ding (BioEnergy Research, 2018)

New pyridocarbazole alkaloids from Strychnos nitida - Wei Li; Gui-Hua Tang; Lin Chen; Ya-Qi Tang; You-Kai Xu; Bo Liu; Sheng Yin (Natural Product Research, 2018)

Investigation of the physical and chemical characteristics of rural solid waste in China and its spatiotemporal distributions - Xiaohui Wu; Bo Yue; Qifei Huang; Qi Wang; Zhilong Li; Yutang Wang; Junying Yu (Environmental Science and Pollution Research, 2018)

Transcription profiling and identification of infection-related genes in Phytophthora cactorum - Xiao-Ren Chen; Shen-Xin Huang; Ye Zhang; Gui-Lin Sheng; Bo-Yue Zhang; Qi-Yuan Li; Feng Zhu; Jing-You Xu (Molecular Genetics and Genomics, 2018)

Biosynthesis of (R)-2-hydroxy-3-phenylpropionic acid using whole recombinant Escherichia coli cells in an aqueous/n-octane biphasic system - Yi-bo Zhu; Yan Xu; Li-mei Wang; Bin Qi (Journal of Zhejiang University-SCIENCE B, 2018)

Muelleria pseudogibbula, a new species from a newly recorded genus (Bacillariophyceae) in China - Qi Liu; Bo Li; Quanxi Wang (Journal of Oceanology and Limnology, 2018)

Development and validation of SSR markers based on transcriptome sequencing of Casuarina equisetifolia - Nan Li; Yong-Qi Zheng; Hong-Mei Ding; He-Peng Li; Hua-Zheng Peng; Bo Jiang; Hai-Bo Li (Trees, 2018)

Effects of Dietary Administration of Shewanella xiamenensis A-1, Aeromonas veronii A-7, and Bacillus subtilis, Single or Combined, on the Grass Carp (Ctenopharyngodon idella) Intestinal Microbiota - Kai Hao; Zhuo-Qi Wu; Dong-Liang Li; Xiao-Bo Yu; Gao-Xue Wang; Fei Ling (Probiotics and Antimicrobial Proteins, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Estrogen-like neuroprotection of isopsoralen against spinal cord injury through estrogen receptor ERα - Xiao-ming Li; Qi Yang; Xu-bo Li; Qiang Cheng; Kun Zhang; Jing Han; Jian-ning Zhao; Gang Liu; Ming-gao Zhao (Metabolic Brain Disease, 2017)

Sinomenine attenuates chronic inflammatory pain in mice - Shuo Li; Jing Han; Dong-sheng Wang; Qi Yang; Bin Feng; Wen-bo Kang; Le Yang; Gang Liu; Ming-gao Zhao (Metabolic Brain Disease, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Hierarchy evaluation of water resources vulnerability under climate change in Beijing, China - Xiao-Hua Yang; Bo-Yang Sun; Jian Zhang; Mei-Shui Li; Jun He; Yi-Ming Wei; Yu-Qi Li (Natural Hazards, 2016)

An all-season sample database for improving land-cover mapping of Africa with two classification schemes - Congcong Li; Peng Gong; Jie Wang; Cui Yuan; Tengyun Hu; Qi Wang; Le Yu; Nicholas Clinton; Mengna Li; Jing Guo; Duole Feng; Conghong Huang; et al. (International Journal of Remote Sensing, 2016)

Occurrence and fate of PBDEs and novel brominated flame retardants in a wastewater treatment plant in Harbin, China - Bo Li; Shao-Jing Sun; Chun-Yan Huo; Wen-Long Li; Ning-Zheng Zhu; Hong Qi; Ling-Jun Kong; Yi-Fan Li; Wan-Li Ma (Environmental Science and Pollution Research, 2016)

BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2016)

Multiple paternity in the common long‐armed octopus Octopus minor (Sasaki, 1920) (Cephalopoda: Octopoda) as revealed by microsatellite DNA analysis - Qi‐Kang Bo; Xiao‐Dong Zheng; Xiao‐Lei Gao; Qi Li (Marine Ecology, 2016)
Multiple paternity was assessed in Octopus minor using microsatellite DNA markers. Octopus minor adults were captured in traps and kept in indoor cement ponds. The females spawned after several days. Ten broods (B1–B10), each containing 15 embryos and the maternal octopus, were maintained until the embryos reached the stage at which DNA could be extracted and used for genotyping. Multiple paternity was tested using five microsatellite DNA markers and the results proved the hypothesis that multiple paternity occurs in O. minor (observed in six out of the 10 broods). Analysis with GERUD software gave the minimum number of fathers and showed that four broods were sired by a single male, three were sired by two different males and three were sired by three different males. In brood B10, the number of fathers identified by the single‐locus method was one fewer than that by the GERUD method. Of the six multiple paternity broods, four (66.7%) showed significant skew from equal paternal contributions, which indicated that sperm competition and/or cryptic female choice may be important for post‐copulatory paternity bias in this species.

Overexpression of sugarcane gene SoSnRK2.1 confers drought tolerance in transgenic tobacco - Thi-Thu Phan; Bo Sun; Jun-Qi Niu; Qin-Liang Tan; Jian Li; Li-Tao Yang; Yang-Rui Li (Plant Cell Reports, 2016)

Erratum to: NFAT5-mediated CACNA1C expression is critical for cardiac electrophysiological development and maturation - Wei Li; Nai-Zhong Zheng; Qi Yuan; Ke Xu; Fan Yang; Lei Gu; Gu-Yan Zheng; Guo-Jie Luo; Chun Fan; Guang-Ju Ji; Bo Zhang; Huiqing Cao; et al. (Journal of Molecular Medicine, 2016)

NFAT5-mediated CACNA1C expression is critical for cardiac electrophysiological development and maturation - Wei Li; Nai-Zhong Zheng; Qi Yuan; Ke Xu; Fan Yang; Lei Gu; Gu-Yan Zheng; Guo-Jie Luo; Chun Fan; Guang-Ju Ji; Bo Zhang; Huiqing Cao; et al. (Journal of Molecular Medicine, 2016)

Site amplification effects as an explanation for the intensity anomaly in the Hanyuan Town during the Wenchuan M w 7.9 earthquake - Hongshuai Liu; Jingshan Bo; Ping Li; Wenhao Qi; Yudong Zhang (Earthquake Engineering and Engineering Vibration, 2016)

The complete mitochondrial genome sequence of Rusa unicolor dejeani (Artiodactyla: Cervidae) - Xiaoya Wu; Yu Qi; Bo Li; Yongfang Yao; Huailiang Xu (Conservation Genetics Resources, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Phosphorylation of Connexin 43 by Cdk5 Modulates Neuronal Migration During Embryonic Brain Development - Guang-Jian Qi; Qiang Chen; Li-Jun Chen; Yang Shu; Lu-Lu Bu; Xiao-Yun Shao; Pei Zhang; Feng-Juan Jiao; Jin Shi; Bo Tian (Molecular Neurobiology, 2016)

The occurrence and fate of siloxanes in wastewater treatment plant in Harbin, China - Bo Li; Wen-Long Li; Shao-Jing Sun; Hong Qi; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Ning-Zheng Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2016)

Economical Succinic Acid Production from Sugarcane Juice by Actinobacillus succinogenes Supplemented with Corn Steep Liquor and Peanut Meal as Nitrogen Sources - Nai-kun Shen; Si-ming Liao; Qing-yan Wang; Yan Qin; Qi-xia Zhu; Jing Zhu; Yi Li; Ri-bo Huang (Sugar Tech, 2016)

Genome-wide association study identifies loci and candidate genes for meat quality traits in Simmental beef cattle - Jiangwei Xia; Xin Qi; Yang Wu; Bo Zhu; Lingyang Xu; Lupei Zhang; Xue Gao; Yan Chen; Junya Li; Huijiang Gao (Mammalian Genome, 2016)

Migration of photoinitiators from paper to fatty food simulants: experimental studies and model application - Bo Han; Li Ding; Rongxin Su; Lei Chen; Libing Wang; Wei Qi; Zhimin He (Food Additives & Contaminants: Part A, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

RETRACTED ARTICLE: Prognostic Significance of Osteopontin and Carbonic Anhydrase 9 in Human Brain Tumors: A Meta-Analysis - Liang-Yu Chen; Li-Bo Liu; Xin-Xing Li; Qi Yu; Bo Yu; Yang Hong; Jian Zheng; Yi-Xue Xue; Yun-Hui Liu (Molecular Neurobiology, 2015)

Evaluation of temporal variations in soil moisture based on the microwave polarization difference index using in situ data over agricultural areas in China - Xiao-Jing Han; Si-Bo Duan; Ronglin Tang; Hai-Qi Liu; Zhao-Liang Li (International Journal of Remote Sensing, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Inhibition of myosin light chain kinase reduces NADPH oxidase-mediated oxidative injury in rat brain following cerebral ischemia/reperfusion - Hong-Feng Zhang; Ting-Bo Li; Bin Liu; Zheng Lou; Jie-Jie Zhang; Jing-Jie Peng; Xiao-Jie Zhang; Qi-Lin Ma; Jun Peng; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Effects of heat stress on serum insulin, adipokines, AMP-activated protein kinase, and heat shock signal molecules in dairy cows - Li Min; Jian-bo Cheng; Bao-lu Shi; Hong-jian Yang; Nan Zheng; Jia-qi Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Enhancement of post-anoxic denitrification for biological nutrient removal: effect of different carbon sources - Hong-bo Chen; Dong-bo Wang; Xiao-ming Li; Qi Yang; Guang-ming Zeng (Environmental Science and Pollution Research, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

Fluid identification based on frequency-dependent AVO attribute inversion in multi-scale fracture media - Cai Liu; Bo-Nan Li; Xu Zhao; Yang Liu; Qi Lu (Applied Geophysics, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Bioactive Equivalence of Combinatorial Components Identified in Screening of an Herbal Medicine - Peng Liu; Hua Yang; Fang Long; Hai-Ping Hao; Xiaojun Xu; Ying Liu; Xiao-Wei Shi; Dan-Dan Zhang; Hao-Chuan Zheng; Qian-Ying Wen; Wen-Wen Li; Hui Ji; et al. (Pharmaceutical Research, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Temperature influence on biological phosphorus removal induced by aerobic/extended-idle regime - Hong-bo Chen; Dong-bo Wang; Xiao-ming Li; Qi Yang; Kun Luo; Guang-ming Zeng (Environmental Science and Pollution Research, 2014)

RNA-seq methods for identifying differentially expressed gene in human pancreatic islet cells treated with pro-inflammatory cytokines - Bo Li; Chang Long Bi; Ning Lang; Yu Ze Li; Chao Xu; Ying Qi Zhang; Ai Xia Zhai; Zhi Feng Cheng (Molecular Biology Reports, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Notch Signaling Activation Promotes Seizure Activity in Temporal Lobe Epilepsy - Longze Sha; Xiaofeng Wu; Yuan Yao; Bo Wen; Jing Feng; Zhiqiang Sha; Xueqin Wang; Xiaoliang Xing; Wanchen Dou; Liri Jin; Wenting Li; Naili Wang; et al. (Molecular Neurobiology, 2014)

Protective effects of oyster extract against hepatic tissue injury in alcoholic liver diseases - Cuiping Zhang; Xiaoyu Li; Xue Jing; Bo Zhang; Qi Zhang; Qinghui Niu; Jianjun Wang; Zibin Tian (Journal of Ocean University of China, 2014)

Synthesis and antitumor activity evaluation of 2-arylisoquinoline-1,3(2H,4H)-diones in vitro and in vivo - Bo-Rui Kang; Juan Wang; Huan Li; Yan Li; Qi-Bing Mei; San-Qi Zhang (Medicinal Chemistry Research, 2014)

Neuroprotective Effects of Bis(7)-tacrine in a Rat Model of Pressure-Induced Retinal Ischemia - Jing-bo Li; Zhi-gang Lu; Li Xu; Qi Wang; Zu-hai Zhang; Jia-hua Fang (Cell Biochemistry and Biophysics, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Fast determination of sulfonamides and their acetylated metabolites from environmental water based on magnetic molecularly imprinted polymers - Haiyan Chen; Yiqun Zhang; Bo Gao; Yang Xu; Qi Zhao; Juan Hou; Jin Yan; Guijie Li; Hui Wang; Lan Ding; Jie Ding; Chun Zhao (Environmental Science and Pollution Research, 2013)

Two new cytotoxic iridoid esters from the rhizomes and roots of Patrinia heterophylla Bunge - Bo Yang; Ru-Bin Cheng; Yi-Qi Wang; Li Shen; Ru-Song Zhang (Natural Product Research, 2013)

CD73+ adipose-derived mesenchymal stem cells possess higher potential to differentiate into cardiomyocytes in vitro - Qiong Li; Li-Jie Qi; Zhi-Kun Guo; He Li; Hong-Bo Zuo; Na-Na Li (Journal of Molecular Histology, 2013)

Cloning of the Xuhuai Goat PPARγ Gene and the Preparation of Transgenic Sheep - Yurong Qin; Hao Chen; Yani Zhang; Caiye Zhu; Bo Gao; Yanhui Yin; Wei Li; Qingqing Shi; Mengmeng Zheng; Qi Xu; Jiuzhou Song; Bichun Li (Biochemical Genetics, 2013)

Marker-assisted selection of Verticillium wilt resistance in progeny populations of upland cotton derived from mass selection-mass crossing - Cheng-Qi Li; Guan-Shen Liu; Hai-Hong Zhao; Li-Juan Wang; Xiao-Fei Zhang; Ying Liu; Wan-Yang Zhou; Liu-Liu Yang; Peng-Bo Li; Qing-Lian Wang (Euphytica, 2013)

Lyssavirus surveillance in bats of southern China’s Guangxi Province - Zhuan-Ling Lu; Wen Wang; Wei-Li Yin; Hai-Bo Tang; Yan Pan; Xiang Liang; Qi Liu; Yi Xiong; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2013)

Pancreatic cystic neoplasms: a review of preoperative diagnosis and management - Xue-li Bai; Qi Zhang; Noman Masood; Waqas Masood; Yun Zhang; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2013)

Overlapping transcription structure of human cytomegalovirus UL140 and UL141 genes - Yanping Ma; Mali Li; Bo Zheng; Ning Wang; Shuang Gao; Lin Wang; Ying Qi; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

Traumatic Brain Injury Induces a Downregulation of MSK1 in Rat Brain Cortex - Bo Ning; Zhen Li; Ningxi Zhu; Gang Hou; Qi Pang (Journal of Molecular Neuroscience, 2013)

The expression of pentraxin 3 and tumor necrosis factor-alpha is increased in preeclamptic placental tissue and maternal serum - Ping Zhou; Xin Luo; Hong-bo Qi; Wen-jun Zong; Hua Zhang; Dan-dan Liu; Qing-shu Li (Inflammation Research, 2012)

Partial antiviral activities of the Asn631 chicken Mx against newcastle disease virus and vesicular stomatitis virus - Bichun Li; Dezhi Fu; Yani Zhang; Qi Xu; Ligang Ni; Guobin Chang; Mengmeng Zheng; Bo Gao; Huaichang Sun; Guohong Chen (Molecular Biology Reports, 2012)

Characterization and virus susceptibility of a skin cell line from red-spotted grouper (Epinephelus akaara) - Xiao-Ying Lei; Zhong-Yuan Chen; Li-Bo He; Chao Pei; Xiu-Ping Yuan; Qi-Ya Zhang (Fish Physiology and Biochemistry, 2012)

Prevalence of and risk factors for subjective symptoms in urban preschool children without a cause identified by the guardian - Bing-Ling Wang; Xi-Ling Li; Xiao-Bo Xu; Yong-Gang Sun; Qi Zhang (International Archives of Occupational and Environmental Health, 2012)

Differential effects of paraoxonase 1 (PON1) polymorphisms on cancer risk: evidence from 25 published studies - Dai-Hua Fang; Cong-Hai Fan; Qiang Ji; Bo-Xiang Qi; Juan Li; Lu Wang (Molecular Biology Reports, 2012)

Identification of a new Bombyx mori nucleopolyhedrovirus and analysis of its bro gene family - Jing-Bo Zhou; Xing-Qi Li; Wanchai De-Eknamkul; Siripuk Suraporn; Jia-Ping Xu (Virus Genes, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Characterization of Prototheca zopfii Associated with Outbreak of Bovine Clinical Mastitis in Herd of Beijing, China - Jian Gao; Han-qi Zhang; Jian-zhong He; Yang-hua He; Shu-mei Li; Rong-guang Hou; Qiao-xing Wu; Yang Gao; Bo Han (Mycopathologia, 2012)

Begomovirus–whitefly mutualism is achieved through repression of plant defences by a virus pathogenicity factor - TONG ZHANG; JUN‐BO LUAN; JIN‐FENG QI; CHANG‐JUN HUANG; MENG LI; XUE‐PING ZHOU; SHU‐SHENG LIU (Molecular Ecology, 2012)
Plant‐mediated interactions between herbivorous arthropods and pathogens transmitted by herbivores are important determinants of the population dynamics of both types of organisms in the field. The role of plant defence in mediating these types of tripartite interactions have been recognized but rarely examined especially at the physiological and molecular levels. Our previous work shows that a worldwide invasive whitefly can establish mutualism with the begomovirus Tomato yellow leaf curl China virus (TYLCCNV) via crop plants. Here, we show that TYLCCNV and betasatellite co‐infection suppresses jasmonic acid defences in the plant. Impairing or enhancing defences mediated by jasmonic acid in the plant enhances or depresses the performance of the whitefly. We further demonstrate that the pathogenicity factor βC1 encoded in the betasatellite is responsible for the initiation of suppression on plant defences and contributes to the realization of the virus–vector mutualism. By integrating ecological, mechanistic and molecular approaches, our study reveals a major mechanism of the plant‐mediated mutualism between a virus and its vector. As the test plant is an important economic crop, the results also have substantial implications for developing novel strategies for management of crop viruses and the insect vectors associated with them.

Determination of aflatoxins in edible oil from markets in Hebei Province of China by liquid chromatography–tandem mass spectrometry - Li-xin Yang; Yin-ping Liu; Hong Miao; Bin Dong; Na-jing Yang; Feng-qi Chang; Li-xue Yang; Jing-bo Sun (Food Additives & Contaminants Part B-Surveillance, 2011)

Gadd45α as an upstream signaling molecule of p38 MAPK triggers oxidative stress-induced sFlt-1 and sEng upregulation in preeclampsia - Xin Luo; Zhen-wei Yao; Hong-bo Qi; Dan-dan Liu; Guo-qing Chen; Shuai Huang; Qing-shu Li (Cell and Tissue Research, 2011)

Intermittent high glucose promotes expression of proinflammatory cytokines in monocytes - Yang Li-bo; Qi Wen-bo; Lv Xiao-hong; Feng You-lun; Zhang Tie (Inflammation Research, 2011)

Analysis of correlation between blood biochemical indicators and bone mineral density of post-menopausal women - Shun-zhi Liu; Li-fang Tian; Peng Xu; Gui-hua Zhuang; Fang Zheng; Juan Tian; Qi-Lan Ning; Bo-Feng Zhu; She-Min Lu; Hong Yan (Molecular Biology Reports, 2011)

Development of a large-scale isolation chamber system for the safe and humane care of medium-sized laboratory animals harboring infectious diseases - Xin Pan; Jian-cheng Qi; Ming Long; Hao Liang; Xiao Chen; Han Li; Guang-bo Li; Hao Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Isolation and characterization of 10 microsatellite loci for White-headed Langur (Trachypithecus leucocephalus) - Sun Tao; Wang Bo-Shi; Liu Zhi-Jin; Huang Cheng-Ming; Zhou Qi-Hai; Li Ming (Conservation Genetics Resources, 2010)

Regulation of Cell Division and Growth in Roots of Lactuca sativa L. Seedlings by the Ent-Kaurene Diterpenoid Rabdosin B - Lan Ding; Hongwei Jing; Bo Qin; Linlin Qi; Jing Li; Tao Wang; Guoan Liu (Journal of Chemical Ecology, 2010)

Evaluation of genetic diversity in Lentinula edodes strains using RAPD, ISSR and SRAP markers - Li-Zhong Fu; Hong-Yu Zhang; Xue-Qian Wu; Hai-Bo Li; Hai-Long Wei; Qing-Qi Wu; Li-An Wang (World Journal of Microbiology and Biotechnology, 2010)

Cytogenetic analysis of reciprocal hybrids and their parents between Larix leptolepis and Larix gmelinii: implications for identifying hybrids - Shou Gong Zhang; Wen Hua Yang; Su Ying Han; Bo Tao Han; Mao Xue Li; Li Wang Qi (Tree Genetics & Genomes, 2010)

Novel microRNAs uncovered by deep sequencing of small RNA transcriptomes in bread wheat (Triticum aestivum L.) and Brachypodium distachyon (L.) Beauv - Bo Wei; Tao Cai; Rongzhi Zhang; Aili Li; Naxin Huo; Shan Li; Yong Q. Gu; John Vogel; Jizeng Jia; Yijun Qi; Long Mao (Functional & Integrative Genomics, 2009)

PEG-conjugated PAMAM Dendrimers Mediate Efficient Intramuscular Gene Expression - Rong Qi; Yu Gao; Yin Tang; Rui-Rui He; Tao-Le Liu; Yun He; Sheng Sun; Bo-Yu Li; Yang-Bing Li; George Liu (The AAPS Journal, 2009)

Curcumin induces apoptosis through the mitochondria-mediated apoptotic pathway in HT-29 cells - Jin-bo Wang; Li-li Qi; Shui-di Zheng; Tian-xing Wu (Journal of Zhejiang University-SCIENCE B, 2009)

Determination of Bioactive Matter by Affinity Adsorption Solid Substrate–Room Temperature Phosphorimetry Based on Lectin Labeled with Self-ordered Ring of Eosin Y - Jia-Ming Liu; Zhen-Bo Liu; Wen-Qi Li; Xiao-Mei Huang; Li-Qing Zeng; Jian Sha; Fei-Ming Li (Journal of Fluorescence, 2009)

Expression of TGH and its role in porcine primary adipocyte lipolysis - Li-Hong Zhang; Li-Jie Zhang; Qi Wang; Bo Wang; Gong-She Yang (Molecular and Cellular Biochemistry, 2008)

Litter pool sizes, decomposition, and nitrogen dynamics in Spartina alterniflora-invaded and native coastal marshlands of the Yangtze Estuary - Cheng Zhang Liao; Yi Qi Luo; Chang Ming Fang; Jia Kuan Chen; Bo Li (Oecologia, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Suppression of colorectal tumor growth by regulated survivin targeting - Binghua Li; Junkai Fan; Xinran Liu; Rong Qi; Linan Bo; Jinfa Gu; Cheng Qian; Xinyuan Liu (Journal of Molecular Medicine, 2006)

Development of a Latex Agglutination Test Using The Major Epitope Domain of Glycoprotein E of Pseudorabies Virus Expressed in E. coli to Differentiate Between Immune Responses in Pigs Naturally Infected or Vaccinated with Pseudorabies Virus - Tang Yong; Chen Huan-chun; Xiao Shao-bo; Qin Ya-li; He Qi-gai; Ren Yu-qi (Veterinary Research Communications, 2005)

Study on index system of assessment of public disaster perception in the western China - Qi Zhou; Jing-yi Li; Jing-bo Zhao (Chinese Geographical Science, 2003)